Observation of wave propagation over 1,000 km into Antarctica winter pack ice - Nose, Takehiko; Katsuno, Tomotaka; Waseda, Takuji; Ushio, Shuki; Rabault, Jean; Kodaira, Tsubasa; Voermans, Joey (Coastal Engineering Journal, 2024)
A drifting wave-ice buoy (Medusa-766) was deployed at the Lützow-Holm Bay (LHB) marginal ice zone in Antarctica during the 63rd Japanese Antarctic Research Expedition to study the wave influence on the unstable LHB fast ice. Medusa-766 survived the Antarctic winter as it was located deep in the ice cover with the shortest distance to the ice-free Southern Ocean over 1,000?km; at this time, there was evidence of 8-cm-height wave signal at the buoy position. Using the the ECMWF?s reanalysis wave data, we show that the incoming waves were likely 4-m waves that were generated by an extratropical cyclone in the Southern Ocean. Wave-induced ice breakup potential for this event could extend hundreds of kilometres into the ice field. When Medusa-766 was in LHB in the summer months, it did not detect sizable wave energy despite the low sea ice concentration extent even during on-ice wave events. Understanding the wave attenuation characteristics is needed to elucidate the ocean wave effect to the unstable LHB fast ice. The success of Medusa-766 demonstrates the robustness of the general design and the high sensitivity of the sensor used, which is promising for future LHB wave?ice interaction research.
Publisher: Taylor & Francis
Keywords: Sørishavet; havis; isshelf

Global biochemical profiling of fast-growing Antarctic bacteria isolated from meltwater ponds by high-throughput FTIR spectroscopy - Akulava, Volha; Tafintseva, Valeria; Blazhko, Uladzislau; Kohler, Achim; Miamin, Uladzislau; Valentovich, Leonid; Shapaval, Volha (PLOS ONE, 2024)
Fourier transform infrared (FTIR) spectroscopy is a biophysical technique used for non-destructive biochemical profiling of biological samples. It can provide comprehensive information about the total cellular biochemical profile of microbial cells. In this study, FTIR spectroscopy was used to perform biochemical characterization of twenty-nine bacterial strains isolated from the Antarctic meltwater ponds. The bacteria were grown on two forms of brain heart infusion (BHI) medium: agar at six different temperatures (4, 10, 18, 25, 30, and 37°C) and on broth at 18°C. Multivariate data analysis approaches such as principal component analysis (PCA) and correlation analysis were used to study the difference in biochemical profiles induced by the cultivation conditions. The observed results indicated a strong correlation between FTIR spectra and the phylogenetic relationships among the studied bacteria. The most accurate taxonomy-aligned clustering was achieved with bacteria cultivated on agar. Cultivation on two forms of BHI medium provided biochemically different bacterial biomass. The impact of temperature on the total cellular biochemical profile of the studied bacteria was species-specific, however, similarly for all bacteria, lipid spectral region was the least affected while polysaccharide region was the most affected by different temperatures. The biggest temperature-triggered changes of the cell chemistry were detected for bacteria with a wide temperature tolerance such Pseudomonas lundensis strains and Acinetobacter lwoffii BIM B-1558.
Publisher: Public Library of Science Article number: e0303298
Keywords: Antarktis; bakterier; biokjemi; mikrobielle organismer; mikrobiologi

Microplastics in Southern Ocean sea ice: a pan-Antarctic perspective - Anna Kelly; Thomas Rodemann; Klaus M. Meiners; Heidi J. Auman; Sebastien Moreau; Francois Fripiat; Bruno Dellile; Delphine Lannuzel (Water Emerging Contaminants & Nanoplastics, 2024)
Microplastic (MP; plastic particles < 5 mm) pollution is pervasive in the marine environment, including remote polar environments. This study provides the first pan-Antarctic survey of MP pollution in Southern Ocean sea ice by analyzing sea ice cores from several diverse Antarctic regions. Abundance, chemical composition, and particle size data were obtained from 19 archived ice core samples. The cores were melted, filtered, and chemically analyzed using Fourier-transform infrared spectroscopy and 4,090 MP particles were identified. Nineteen polymer types were found across all samples, with an average concentration of 44.8 (± 50.9) particles·L-1. Abundance and composition varied with ice type and geographical location. Pack ice exhibited significantly higher particle concentrations than landfast ice, suggesting open ocean sources of pollution. Winter sea ice cores had significantly more MPs than spring and summer-drilled cores, suggesting ice formation processes play a role in particle incorporation. Smaller particles dominated across samples. Polyethylene (PE) and polypropylene (PP) were the most common polymers, mirroring those most identified across marine habitats. Higher average MP concentrations in developing sea ice during autumn and winter, contrasting lower levels observed in spring and summer, suggest turbulent conditions and faster growth rates are likely responsible for the increased incorporation of particles. Southern Ocean MP contamination likely stems from both local and distant sources. However, the circulation of deep waters and long-range transport likely contribute to the accumulation of MPs in regional gyres, coastlines, and their eventual incorporation into sea ice. Additionally, seasonal sea ice variations likely influence regional polymer compositions, reflecting the MP composition of the underlying waters.
Keywords: Sørishavet; forurensning; havis; iskjerner; mikroplast; sjøis

Field comparison of Antarctic krill (Euphausia superba) backscatter and aggregation types using NORTEK and SIMRAD echosounders - Annasawmy, Pavanee; Horne, John K.; Reiss, Christian S.; Cutter, George R.; Macaulay, Gavin J. (ICES Journal of Marine Science, 2024)
Temporal distributions of Antarctic krill (Euphausia superba) density and aggregation types were characterized and compared using Nortek Signature100 and SIMRAD Wideband Autonomous Transceiver (WBAT) upward-looking echosounders. Noise varied between the two echosounders. With the Signature100, it was necessary to correct data for background, transient, and impulse noises, while the WBAT data needed to be corrected for background noise only. For selected regions with no visible backscatter, the signal-to-noise ratio of Sv values (i.e. the ratio between the signal and the background noise level) did not vary between the two echosounders. Surface echo backscatter was similar during similar time periods. Descriptive metrics were used to quantify spatial and temporal krill vertical distributions: volume backscatter, mean depth, center of mass, inertia, equivalent area, aggregation index, and proportion occupied. Krill backscatter density differed between the two instruments but was detected at similar mean depths. Krill aggregations were identified at each mooring location and classified in three types based on morphological characteristics. Each type of aggregation shape differed at the two spatially separated moorings, while the acoustic density of each aggregation type was similar. The Signature100 detected a lower number of krill aggregations (n = 133) compared to the WBAT (n = 707). Although both instruments can be used for autonomous deployment and sampling of krill over extended periods, there is a strong caveat for the use of the Signature100 due to significant differences in noise characteristics and krill detection.
Keywords: Sørishavet; dataanalyse; ekkolodd; fiskerier; krill; marin biologi; plankton

Characterizing Antarctic air-breathing predator dive patterns on a common prey base from stationary echosounders - Annasawmy, Pavanee; Horne, John K.; Reiss, Christian S.; Macaulay, Gavin J. (Polar Science, 2024)
Diving patterns of air-breathing predators were monitored from three moored subsurface upward-looking echosounders. Complete and partial dive profiles were visible on active acoustic records as echoes that started and/or returned to the surface. Dive metrics: maximum dive depths, durations, and wiggle count were measured and angles, distances, and velocities, were calculated at each site. Dive shapes ‘U’, ‘V’ and ‘W’ were derived using the number of wiggles and the percentage of dive bottom time. Dive profiles were classified into four types with type 1 dives being short in total duration and distance, low velocities, small angles, shallow, and linked to ‘U’ and ‘W’ shapes. Type 2 dives were short in distance, had low velocities, shallow depths, and were linked to ‘V’ dives. Dive types 3 and 4 had higher velocities, larger angles, longer total durations, and were deeper than types 1 and 2. Observed dive types could correspond to travelling, exploring, and foraging predator behaviors. Significant predator-prey overlaps occurred with predator dive profile counts correlated with krill aggregation thickness, density, and depth. This study demonstrates the utility of using stationary active acoustics to identify predator dive profiles with a simultaneous characterization of the potential prey field.
Article number: 100974
Keywords: Deceptionøya; Sør-Shetlandsøyene; Sørishavet; batymetri; hydroakustikk; marin biologi; marine økosystemer; oseanografi

Seasonal acoustic presence of marine mammals at the South Orkney Islands, Scotia Sea - Åsvestad, Linn; Ahonen, Heidi; Menze, Sebastian; Lowther, Andrew; Lindstrøm, Ulf; Krafft, Bjørn A. (Royal Society Open Science, 2024)
Increased knowledge about marine mammal seasonal distribution and species assemblage from the South Orkney Islands waters is needed for the development of management regulations of the commercial fishery for Antarctic krill (Euphausia superba) in this region. Passive acoustic monitoring (PAM) data were collected during the autumn and winter seasons in two consecutive years (2016, 2017), which represented highly contrasting environmental conditions due to the 2016 El Niño event. We explored differences in seasonal patterns in marine mammal acoustic presence between the two years in context of environmental cues and climate variability. Acoustic signals from five baleen whale species, two pinniped species and odontocete species were detected and separated into guilds. Although species diversity remained stable over time, the ice-avoiding and ice-affiliated species dominated before and after the onset of winter, respectively, and thus demonstrating a shift in guild composition related to season. Herein, we provide novel information about local marine mammal species diversity, community structure and residency times in a krill hotspot. Our study also demonstrates the utility of PAM data and its usefulness in providing new insights into the marine mammal habitat use and responses to environmental conditions, which are essential knowledge for the future development of a sustainable fishery management in a changing ecosystem.
_eprint: https://royalsocietypublishing.org/doi/pdf/10.1098/rsos.230233
Keywords: Sørishavet; marin biologi; pattedyr; zoologi

Outlining three arguments for Rights of Antarctica - Baard, Patrik; Mancilla, Alejandra (The Polar Journal, 2024)
In this article, we investigate three arguments for Rights of Antarctica (RoA), understood as recognising the whole continent as a rights-holder with legal standing. For this, we draw inspiration from the Antarctica Declaration, a text developed by an interdisciplinary and international group of scholars and activists. We scrutinise three justifications that could potentially be used in support of RoA. First, we investigate whether arguments for Rights of Nature (RoN) elsewhere can support RoA. RoN has been accepted in several domestic legislations. Unfortunately, we discover important disanalogies between RoA and RoN, defeating the purpose of justifying RoA with reference to RoN. Second, we scrutinise potential arguments that focus on giving rights to specific Antarctic ecoregions or places. However, such arguments would only cover parts of the continent, thus going against the holistic approach of RoA, and they would require using a broader understanding of ?attachments? as grounds for justifying rights for parts of Antarctica. In contrast, we construct an argument for accepting RoA based on four components: (1) Antarctica?s intrinsic value, (2) wider forms of human attachments, (3) Antarctica?s substantial role as a global systemic resource, and (4) the fact that Antarctica is under recurrent and substantial threats. While none of these are individually sufficient for recognising RoA, they can jointly make RoA appropriate. We conclude that it remains an open question whether international law or, more specifically, the Antarctic Treaty, would be open to such conceptual and normative innovation, adopting a new paradigm in our treatment of the nonhuman natural world. At the same time, we hope to kickstart a discussion of what RoA would require and how it should relate more generally to RoN discourses.
Publisher: Routledge
Keywords: Antarktis; Antarktistraktaten; jus

Sources of low-frequency variability in observed Antarctic sea ice - Bonan, D. B.; Dörr, J.; Wills, R. C. J.; Thompson, A. F.; Årthun, M. (The Cryosphere, 2024)
Antarctic sea ice has exhibited significant variability over the satellite record, including a period of prolonged and gradual expansion, as well as a period of sudden decline. A number of mechanisms have been proposed to explain this variability, but how each mechanism manifests spatially and temporally remains poorly understood. Here, we use a statistical method called low-frequency component analysis to analyze the spatiotemporal structure of observed Antarctic sea ice concentration variability. The identified patterns reveal distinct modes of low-frequency sea ice variability. The leading mode, which accounts for the large-scale, gradual expansion of sea ice, is associated with the Interdecadal Pacific Oscillation and resembles the observed sea surface temperature trend pattern that climate models have trouble reproducing. The second mode is associated with the central Pacific El Niño–Southern Oscillation (ENSO) and the Southern Annular Mode and accounts for most of the sea ice variability in the Ross Sea. The third mode is associated with the eastern Pacific ENSO and Amundsen Sea Low and accounts for most of the pan-Antarctic sea ice variability and almost all of the sea ice variability in the Weddell Sea. The third mode is also related to periods of abrupt Antarctic sea ice decline that are associated with a weakening of the circumpolar westerlies, which favors surface warming through a shoaling of the ocean mixed layer and decreased northward Ekman heat transport. Broadly, these results suggest that climate model biases in long-term Antarctic sea ice and large-scale sea surface temperature trends are related to each other and that eastern Pacific ENSO variability is a key ingredient for abrupt Antarctic sea ice changes.
Publisher: Copernicus Publications
Keywords: Sørishavet; havis; klimamodeller; klimatologi; meteorologi; oseanografi; sjøis

Glacial–interglacial Circumpolar Deep Water temperatures during the last 800 000 years: estimates from a synthesis of bottom water temperature reconstructions - Chandler, D. M.; Langebroek, Petra M. (Clim. Past, 2024)
Future climate and sea level projections depend sensitively on the response of the Antarctic Ice Sheet to ocean-driven melting and the resulting freshwater fluxes into the Southern Ocean. Circumpolar Deep Water (CDW) transport across the Antarctic continental shelf and into cavities beneath ice shelves is increasingly recognised as a crucial heat source for ice shelf melt. Quantifying past changes in the temperature of CDW is therefore of great benefit for modelling ice sheet response to past warm climates, for validating paleoclimate models, and for putting recent and projected changes in CDW temperature into context. Here we compile the available bottom water temperature reconstructions representative of CDW over the past 800 kyr. Estimated interglacial warming reached anomalies of +0.6 +/- 0.4 degrees C (MIS 11) and +0.5 +/- 0.5 degrees C (MIS 5) relative to present. Glacial cooling typically reached anomalies of ca. -1.5 to -2 degrees C, therefore maintaining positive thermal forcing for ice shelf melt even during glacials in the Amundsen Sea region of West Antarctica. Despite high variance amongst a small number of records and poor (4 kyr) temporal resolution, we find persistent and close relationships between our estimated CDW temperature and Southern Ocean sea surface temperature, Antarctic surface air temperature, and global deep-water temperature reconstructions at glacial-cycle timescales. Given the important role that CDW plays in connecting the world's three main ocean basins and in driving Antarctic Ice Sheet mass loss, additional temperature reconstructions targeting CDW are urgently needed to increase temporal and spatial resolution and to decrease uncertainty in past CDW temperatures - whether for use as a boundary condition, for model validation, or for understanding past oceanographic changes.
Publisher: Copernicus Publications
Keywords: Sørishavet; klimamodeller; klimatologi; oseanografi; paleoklimatologi

Shackletons svanesang, Shackleton-Rowett-ekspedisjonen 1921-22 - Chojecki, Jan (Polarboken, 2024)
Keywords: Sørishavet; ekspedisjoner; historie

Observations of the Antarctic Slope Current in the Southeastern Weddell Sea: A Bottom-Enhanced Current and Its Seasonal Variability - Darelius, Elin; Fer, Ilker; Janout, Markus; Daae, Kjersti; Steiger, Nadine (Journal of Geophysical Research: Oceans, 2024)
Abstract The Antarctic Slope Front and the associated Antarctic Slope Current dynamically regulate the exchanges of heat across the continental shelf break around Antarctica. Where the front is weak, relatively warm deep waters reach the ice shelf cavities, contributing to basal melting and ultimately affecting sea level rise. Here, we present new 2017?2021 records from two moorings deployed on the upper continental slope (530 and 738 m depth) just upstream of the Filchner Trough in the southeastern Weddell Sea. The structure and seasonal variability of the frontal system in this region, central to the inflow of warm water toward the large Filchner-Ronne Ice Shelf, is previously undescribed. We use the records to describe the mean state and the seasonal variability of the regional hydrography and the southern part of the Antarctic Slope Current. We find that (a) the current is, contrary to previous assumptions, bottom-enhanced, (b) the isotherms slope upwards toward the shelf break, and more so for warmer isotherms, and (c) the monthly mean thermocline depth is shallowest in February-March and deepest in May-June while (d) the current is strongest in April-June. On monthly timescales, we show that (e) positive temperature anomalies of the de-seasoned records are associated with weaker-than-average currents. We propose that the upward-sloping isotherms are linked to the local topography and conservation of potential vorticity. Our results contribute to the understanding of how warm ocean waters propagate southward and potentially affect basal melt rates at the Filchner-Ronne Ice Shelf.
Publisher: John Wiley & Sons, Ltd Article number: e2023JC020666
Keywords: Sørishavet; Weddellhavet; havstrømmer; oseanografi

A virtual geobibliography of polar tourism and climate change - Demiroglu, O. Cenk; Bohn, Dorothee; Dannevig, Halvor; Hall, C. Michael; Hehir, Christy; Lundmark, Linda; Nilsson, Robert O.; Olsen, Julia; Tervo-Kankare, Kaarina; Vereda, Marisol; Welling, Johannes (Journal of Sustainable Tourism, 2024)
The polar regions are increasingly at the center of attention as the hot spots of climate crisis as well as tourism development. The recent IPCC reports highlight several climate change risks for the rather carbon-intensive and weather-based/dependent polar tourism industry in the Arctic and the Antarctic. This study presents the scholarly state-of-knowledge on tourism and climate change in the polar regions with a literature survey extending beyond the Anglophone publications. As a supporting tool, we provide a live web GIS application based on the geographical coverages of the publications and filterable by various spatial, thematic and bibliographical attributes. The final list of 137 publications indicates that, regionally, the Arctic has been covered more than the Antarctic, whilst an uneven distribution within the Arctic also exists. In terms of the climate change risks themes, climate risk research, i.e. impact and adaptation studies, strongly outnumbers the carbon risk studies especially in the Arctic context, and, despite a balance between the two main risk themes, climate risk research in the Antarctic proves itself outdated. Accordingly, the review ends with a research agenda based on these spatial and thematic gaps and their detailed breakdowns.
Publisher: Routledge
Keywords: Antarktis; bibliografi; geobibliografi; klimaendringer; polarområdene; turisme

Southern Ocean sea ice, icebergs, and meteorological data from maritime sources for the period 1929 to 1940 - Divine, Dmitry V.; Divina, Svetlana; Bjørge, Ole Edvard; Isaksson, Elisabeth; Jølle, Harald Dag; Stokkeland, Ivar; Vasquez Guzman, Mariela; Wilkinson, Sally; Wilkinson, Clive (Geoscience Data Journal, 2024)
Maritime historical documentary sources of weather and state of sea surface including sea ice can aid in filling a known climate knowledge gap for the Southern Ocean and Antarctica for the first half of the 20th century. This study presents a data set of marine climate, sea ice and icebergs recovered from a collection of logbooks from mainly Norwegian whaling factory ships that operated in the Southern Ocean during 1929-1940. The data set comprises some 8000 weather and 4000 sea ice/open sea records from austral summers of the study period. This paper further discusses the structure and content of most common Norwegian maritime documentary sources of the period along with the practices of logging information relevant for the study, such as time keeping, positioning and making weather observations. An emphasis was made on recovery of notes on sea ice and icebergs and their interpretation in terms of WMO categories of sea ice concentration. Data, including ship-related metadata from all individual documents are homogenized and structured to a common machine-readable format that simplifies its ingestion into relevant climate data depositories.
Publisher: John Wiley & Sons, Ltd
Keywords: Sørishavet; hvalfangst; isberg; klima; meteorologi; sjøis; skipsloggbøker

Early aerial expedition photos reveal 85 years of glacier growth and stability in East Antarctica - Dømgaard, Mads; Schomacker, Anders; Isaksson, Elisabeth; Millan, Romain; Huiban, Flora; Dehecq, Amaury; Fleischer, Amanda; Moholdt, Geir; Andersen, Jonas K.; Bjørk, Anders A. (Nature Communications, 2024)
During the last few decades, several sectors in Antarctica have transitioned from glacial mass balance equilibrium to mass loss. In order to determine if recent trends exceed the scale of natural variability, long-term observations are vital. Here we explore the earliest, large-scale, aerial image archive of Antarctica to provide a unique record of 21 outlet glaciers along the coastline of East Antarctica since the 1930s. In Lützow-Holm Bay, our results reveal constant ice surface elevations since the 1930s, and indications of a weakening of local land-fast sea-ice conditions. Along the coastline of Kemp and Mac Robertson, and Ingrid Christensen Coast, we observe a long-term moderate thickening of the glaciers since 1937 and 1960 with periodic thinning and decadal variability. In all regions, the long-term changes in ice thickness correspond with the trends in snowfall since 1940. Our results demonstrate that the stability and growth in ice elevations observed in terrestrial basins over the past few decades are part of a trend spanning at least a century, and highlight the importance of understanding long-term changes when interpreting current dynamics.
Article number: 4466
Keywords: Antarktis; Thorshavn ekspedisjon; flyfotografering; geografi; glasiologi; kartlegging; klimaendringer; klimatologi; kryosfæren; topografi

Conjugate aurora observations by the Gjøa and Discovery expeditions - Egeland, Alv (Hist. Geo Space. Sci., 2024)
From 1901 to 1912 – known as the “heroic period” of Arctic and Antarctic exploration – great inroads were made (not only geographic but also scientific) to our knowledge of the continent. At Amundsen's Expedition through the Northwest Passage, measurements of the geomagnetic field and visual auroras were carried out for 19 months at Gjoa Haven (Gjøahavn in Norwegian; geographic coordinates 68°37′10′′ N, 95°53′25′′ W). Scott's Discovery Expedition – at Cape Armitage, McMurdo (coordinates 77.86° S, 166.69° E), Antarctica – carried out the same type of measurements. Their observations were carried out geomagnetically conjugate to Gjoa Haven, with both stations close to 78° magnetic latitude. In addition, measurements were overlapping in time during 1903–1904. However, these two stations are located at different longitudes, so there is a difference in local time between the stations of about 6.5 h. Gjoa Haven and Cape Armitage are conveniently located for separating disturbances in the polar cap regions caused by solar electromagnetic radiations or the solar wind. Auroras were observed during 7 months per year. This gave a unique possibility to compare conjugate characteristics of polar cap auroras. Comparing conjugate geophysical data introduces some difficulties. During the winter season at Gjoa Haven, they had a bright summer in Antarctica, and visa versa. Thus, simultaneous temporal and spatial ionospheric variations can be marked differently. Still, the average diurnal and seasonal variations were similar. The quantity of the auroral data from Cape Armitage was larger because there they had a continuous watch of the sky. The main findings regarding polar cap auroras are the following. Three different auroral forms dominate the polar cap. Low-intensity auroral bands – then called streamers – were the dominating auroral forms morning and afternoon. The number of auroral events in 1903 was nearly twice that in 1902 and 1904. A marked midwinter maximum was observed at both stations. Many displays were observed poleward of the oval. The large fraction was associated with weak magnetic disturbances. Some forms of polar cap aurora have special magnetic signatures and seem to be anti-correlated with Kp. They can be mapped even if they are not seen. According to recent satellite measurements (Newell et al., 2009), they are probably caused by polar rain and/or photoelectrons.
Publisher: Copernicus Publications
Keywords: Antarktis; Discoveryekspedisjonen; fysikk; polarfarere; polarområdene; romfysikk; sørlys

Features and processes of rock weathering in central Dronning Maud Land, Antarctica - Elvevold, Synnøve; Engvik, Ane K.; Sunde, Øyvind (Geomorphology, 2024)
In this study, we have investigated rock weathering phenomena in the central part of Dronning Maud Land, Antarctica. The area is characterized by low mean annual temperatures (−18 °C), strong katabatic winds, and minimal liquid water at the surface. Weathering features, including ventifacts, tafoni, and grus accumulations, are characterized through field observations, rock surface temperature measurements, and microscopic analysis. Abrasion by sand and ice particles transported by strong winds has locally resulted in ridge-shaped ventifacts and rock surfaces with elongated pits, furrows, and grooves. The abrasion-caused features, such as polished facets, keels, and grooves, indicate a northeast-facing wind direction, aligning with the present-day wind regime. The dominant weathering processes in coarse-grained intrusive rocks are oxidation and granular disintegration. Fe-oxidation induces cracking, increasing the porosity and enhancing susceptibility to further weathering. Additionally, temperature fluctuations on rock surfaces caused by solar radiation create thermal stress, which can lead to the formation of microcracks. These microcracks, formed due to thermal expansion, are likely to propagate through subcritical cracking, which is a slow, long-term process. Together, Fe-oxidation, thermal expansion, and subcritical cracking are important mechanisms contributing to long-term weathering and rock decay. Salt weathering, facilitated by snow and ice meltwater, particularly within tafoni, leads to flaking and disintegration of the parent rock. These findings shed light on the complex interactions shaping the geomorphology of central Dronning Maud Land and provide insights into long-term weathering processes operating in Antarctica's extreme environment.
Article number: 109435
Keywords: Dronning Maud Land; geologi; geomorfologi

Mineralogical and Geochemical Response to Fluid Infiltration into Cambrian Orthopyroxene-Bearing Granitoids and Gneisses, Dronning Maud Land, Antarctica - Engvik, Ane K.; Corfu, Fernando; Kleinhanns, Ilka C.; Taubald, Heinrich; Elvevold, Synnøve (Minerals, 2024)
Fluid infiltration into Proterozoic and Early Palaeozoic dry, orthopyroxene-bearing granitoids and gneisses in Dronning Maud Land, Antarctica, has caused changes to rock appearance, mineralogy, and rock chemistry. The main mineralogical changes are the replacement of orthopyroxene by hornblende and biotite, ilmenite by titanite, and various changes in feldspar structure and composition. Geochemically, these processes resulted in general gains of Si, mostly of Al, and marginally of K and Na but losses of Fe, Mg, Ti, Ca, and P. The isotopic oxygen composition (δ18OSMOW = 6.0‰–9.9‰) is in accordance with that of the magmatic precursor, both for the host rock and infiltrating fluid. U-Pb isotopes in zircon of the altered and unaltered syenite to quartz-monzonite indicate a primary crystallization age of 520.2 ± 1.0 Ma, while titanite defines alteration at 485.5 ± 1.4 Ma. Two sets of gneiss samples yield a Rb-Sr age of 517 ± 6 Ma and a Sm-Nd age of 536 ± 23 Ma. The initial Sr and Nd isotopic ratios suggest derivation of the gneisses from a relatively juvenile source but with a very strong metasomatic effect that introduced radiogenic Sr into the system. The granitoid data indicate instead a derivation from Mid-Proterozoic crust, probably with additions of mantle components.
Keywords: Dronning Maud Land; NARE 1996/97; geokjemi; geokronologi; geologi; mineralogi

Observed water-mass characteristics and circulation off Prydz Bay, East Antarctica - Foppert, Annie; Bestley, Sophie; Shadwick, Elizabeth H.; Klocker, Andreas; Vives, Clara R.; Liniger, Guillaume; Westwood, Karen J. (Frontiers in Marine Science, 2024)
Circulation and water masses in the greater Prydz Bay region were surveyed in the austral summer 2021 (January-March) during the ‘Trends in Euphausiids off Mawson, Predators and Oceanography’ (TEMPO) experiment, and are described in this paper. The Southern Antarctic Circumpolar Current Front is found in the northern part of the survey area, generally near 63-64°S, whereas the Southern Boundary Front is located between 64 and 65.5°S. The westward flowing Antarctic Slope Front (ASF) is found in the southern part of the survey area near the continental slope on most transects. Highest concentrations of oxygen (> 300 µmol kg−1) are found in shelf waters at stations in Prydz Bay, south of 67°S along 75°E, whereas the lowest oxygen values are found in the Circumpolar Deep Water layer, with an average of roughly 215 µmol kg−1. North of the northern extension of the ASF, surface mixed layers are between 20 and 60 m deep. Mixed layers tend to deepen slightly in the northern part of the survey, generally increasing north of 64°S where the ocean has been ice-free the longest. We find evidence of upwelling of waters into the surface layers, based on temperature anomaly, particularly strong along 80°E. Enhanced variability of biogeochemical properties - nutrients, DIC, DO - in the AASW layer is driven by a combination of sea-ice and biological processes. Antarctic Bottom Water, defined as water with neutral density > 28.3 kg m-3, was sampled at all the offshore full-depth stations, with a colder/fresher variety along western transects and a warmer/saltier variety in the east. Newly formed Antarctic Bottom Water – the coldest, freshest, and most recently ventilated – is mostly found in the deep ocean along 65°E, in the base of the Daly Canyon.
Keywords: AABW; Sørishavet; klimatologi; oseanografi; vannmasser

An Assessment of Subseasonal Prediction Skill of the Antarctic Sea Ice Edge - Gao, Yuchun; Xiu, Yongwu; Nie, Yafei; Luo, Hao; Yang, Qinghua; Zampieri, Lorenzo; Lv, Xianqing; Uotila, Petteri (Journal of Geophysical Research: Oceans, 2024)
Abstract In this study, the subseasonal Antarctic sea ice edge prediction skill of the Copernicus Climate Change Service (C3S) and Subseasonal to Seasonal (S2S) projects was evaluated by a probabilistic metric, the spatial probability score (SPS). Both projects provide subseasonal to seasonal scale forecasts of multiple coupled dynamical systems. We found that predictions by individual dynamical systems remain skillful for up to 38 days (i.e., the ECMWF system). Regionally, dynamical systems are better at predicting the sea ice edge in the West Antarctic than in the East Antarctic. However, the seasonal variations of the prediction skill are partly system-dependent as some systems have a freezing-season bias, some had a melting-season bias, and some had a season-independent bias. Further analysis reveals that the model initialization is the crucial prerequisite for skillful subseasonal sea ice prediction. For those systems with the most realistic initialization, the model physics dictates the propagation of initialization errors and, consequently, the temporal length of predictive skill. Additionally, we found that the SPS-characterized prediction skill could be improved by increasing the ensemble size to gain a more realistic ensemble spread. Based on the C3S systems, we constructed a multi-model forecast from the above principles. This forecast consistently demonstrated a superior prediction skill compared to individual dynamical systems or statistical observation-based benchmarks. In summary, our results elucidate the most important factors (i.e., the model initialization and the model physics) affecting the currently available subseasonal Antarctic sea ice prediction systems and highlighting the opportunities to improve them significantly.
Publisher: John Wiley & Sons, Ltd
Keywords: Sørishavet; havis; klimaendringer; klimatologi; oseanografi; sjøis

Museomics analyses inform about Channichthys icefish species diversity - Garmann-Aarhus, Benedicte; Nikolaeva, Ekaterina; Desvignes, Thomas; Straube, Nicolas; Matschiner, Michael (bioRxiv, 2024)
The rapid diversification of notothenioid fishes in the waters surrounding the Antarctic continent is a prime example of the process of adaptive radiation. Within around 10 million years, Antarctic notothenioids have diversified into over 100 species with a broad range of lifestyles and ecological adaptations. However, the exact number of species within this radiation has long been unclear. Particularly challenging is the taxonomy of the genus Channichthys, for which between one and nine species have been recognized by different authors. The putative species from this genus are known from a limited number of representative specimens, of which most were sampled decades ago. Here, we investigated the mitochondrial genomes of museum specimens representing the four recently recognized species Unicorn Icefish (C. rhinoceratus), Red Icefish (C. rugosus), Sailfish Pike (C. velifer), and Charcoal Icefish (C. panticapaei), complemented by morphological analyses. All analyzed specimens were collected in the 1960s and 1970s and fixed in formaldehyde, and their DNA has thus been heavily degraded. Applying ancient-DNA protocols for DNA extraction and single-stranded library preparation, we were nevertheless able to obtain sufficient endogenous DNA to reconstruct the mitochondrial genomes of one specimen of each species. These mitochondrial genome sequences were nearly identical for the three specimens assigned to Unicorn Icefish, Red Icefish, and Sailfish Pike, while greater mitochondrial divergence was observed for the Charcoal Icefish specimens. We discuss possible explanations of the contrast between these molecular results and the recognizable morphological variation found among the four species, and recommend that at least the Charcoal Icefish be included the list of valid icefish and notothenioid species.Competing Interest StatementThe authors have declared no competing interest.
Article Number: 32
Keywords: Sørishavet; fisker; genetisk analyse; marin biologi; morfologi; taksonomi; zoologi; økologi

Machine learning applied to species occurrence and interactions: the missing link in biodiversity assessment and modelling of Antarctic plankton distribution - Grillo, Marco; Schiaparelli, Stefano; Durazzano, Tiziana; Guglielmo, Letterio; Granata, Antonia; Huettmann, Falk (Ecological Processes, 2024)
Background: Plankton is the essential ecological category that occupies the lower levels of aquatic trophic networks, representing a good indicator of environmental change. However, most studies deal with distribution of single spe- cies or taxa and do not take into account the complex of biological interactions of the real world that rule the ecologi- cal processes. Results: This study focused on analyzing Antarctic marine phytoplankton, mesozooplankton, and microzooplankton, examining their biological interactions and co-existences. Field data yielded 1053 biological interaction values, 762 coexistence values, and 15 zero values. Six phytoplankton assemblages and six copepod species were selected based on their abundance and ecological roles. Using 23 environmental descriptors, we modelled the distribution of taxa to accurately represent their occurrences. Sampling was conducted during the 2016–2017 Italian National Antarctic Programme (PNRA) ‘P-ROSE’ project in the East Ross Sea. Machine learning techniques were applied to the occurrence data to generate 48 predictive species distribution maps (SDMs), producing 3D maps for the entire Ross Sea area. These models quantitatively predicted the occurrences of each copepod and phytoplankton assemblage, providing crucial insights into potential variations in biotic and trophic interactions, with significant implications for the man- agement and conservation of Antarctic marine resources. The Receiver Operating Characteristic (ROC) results indi- cated the highest model efficiency, for Cyanophyta (74%) among phytoplankton assemblages and Paralabidocera antarctica (83%) among copepod communities. The SDMs revealed distinct spatial heterogeneity in the Ross Sea area, with an average Relative Index of Occurrence values of 0.28 (min: 0; max: 0.65) for phytoplankton assemblages and 0.39 (min: 0; max: 0.71) for copepods. Conclusion: The results of this study are essential for a science-based management for one of the world’s most pris- tine ecosystems and addressing potential climate-induced alterations in species interactions. Our study emphasizes the importance of considering biological interactions in planktonic studies, employing open access and machine learning for measurable and repeatable distribution modelling, and providing crucial ecological insights for informed conservation strategies in the face of environmental change.
Article number: 56 (2024)
Keywords: Rosshavet; Sørishavet; biodiversitet; fytoplankton; marin biologi

Short- and long-term variability of the Antarctic and Greenland ice sheets - Hanna, Edward; Topál, Dániel; Box, Jason E.; Buzzard, Sammie; Christie, Frazer D. W.; Hvidberg, Christine; Morlighem, Mathieu; De Santis, Laura; Silvano, Alessandro; Colleoni, Florence; Sasgen, Ingo; Banwell, Alison F.; et al. (Nature Reviews Earth & Environment, 2024)
The variability of the Antarctic and Greenland ice sheets occurs on various timescales and is important for projections of sea level rise; however, there are substantial uncertainties concerning future ice-sheet mass changes. In this Review, we explore the degree to which short-term fluctuations and extreme glaciological events reflect the ice sheets’ long-term evolution and response to ongoing climate change. Short-term (decadal or shorter) variations in atmospheric or oceanic conditions can trigger amplifying feedbacks that increase the sensitivity of ice sheets to climate change. For example, variability in ocean-induced and atmosphere-induced melting can trigger ice thinning, retreat and/or collapse of ice shelves, grounding-line retreat, and ice flow acceleration. The Antarctic Ice Sheet is especially prone to increased melting and ice sheet collapse from warm ocean currents, which could be accentuated with increased climate variability. In Greenland both high and low melt anomalies have been observed since 2012, highlighting the influence of increased interannual climate variability on extreme glaciological events and ice sheet evolution. Failing to adequately account for such variability can result in biased projections of multi-decadal ice mass loss. Therefore, future research should aim to improve climate and ocean observations and models, and develop sophisticated ice sheet models that are directly constrained by observational records and can capture ice dynamical changes across various timescales.
Keywords: Antarktis; glasiologi; innlandsis; klimaendringer; polarområdene

Drivers of phytoplankton distribution, abundance and community composition off East Antarctica, from 55-80°E (CCAMLR Division 58.4.2 East) - Heidemann, Asta C.; Westwood, Karen J.; Foppert, Annie; Wright, Simon W.; Klocker, Andreas; Vives, Clara R.; Wotherspoon, Simon; Bestley, Sophie (Frontiers in Marine Science, 2024)
Southern Ocean phytoplankton form the base of the Antarctic food web, influencing higher trophic levels through biomass and community structure. We examined phytoplankton distribution and abundance in the Indian Sector of the Southern Ocean during austral summer as part a multidisciplinary ecosystem survey: Trends in Euphausiids off Mawson, Predators and Oceanography (TEMPO, 2021). Sampling covered six meridional transects from 55-80°E, and from 62°S or 63°S to the ice edge. To determine phytoplankton groups, CHEMTAX analysis was undertaken on pigments measured using HPLC. Diatoms were the dominant component of phytoplankton communities, explaining 56% of variation in chlorophyll a (Chl a), with haptophytes also being a major component. Prior to sampling the sea ice had retreated in a south-westerly direction, leading to shorter ice-free periods in the west (< 44 days, ≤65°E) compared to east (> 44 days, ≥70°E), inducing a strong seasonal effect. The east was nutrient limited, indicated by low-iron forms of haptophytes, and higher silicate:nitrate drawdown ratios (5.1 east vs 4.3 west), pheophytin a (phaeo) concentrations (30.0 vs 18.4 mg m-2) and phaeo:Chl a ratios (1.06 vs 0.53). Biological influences were evident at northern stations between 75-80°E, where krill “super-swarms” and feeding whales were observed. Here, diatoms were depleted from surface waters likely due to krill grazing, as indicated by high phaeo:Chl a ratios (> 0.75), and continued presence of haptophytes, associated with inefficient filtering or selective grazing by krill. Oceanographic influences included deeper mixed layers reducing diatom biomass, and a bloom to the north of the southern Antarctic Circumpolar Current Front in the western survey area thought to be sinking as waters flowed from west to east. Haptophytes were influenced by the Antarctic Slope Front with high-iron forms prevalent to the south only, showing limited iron transfer from coastal waters. Cryptophytes were associated with meltwater, and greens (chlorophytes + prasinophytes) were prevalent below the mixed layer. The interplay of seasonal, biological and oceanographic influences on phytoplankton populations during TEMPO had parallels with processes observed in the BROKE and BROKE-West voyages conducted 25 and 15 years earlier, respectively. Our research consolidates understanding of the krill ecosystem to ensure sustainable management in East Antarctic waters.
Keywords: Sørishavet; fytoplankton; krill; marin biologi; marine økosystemer; oseanografi; phytoplankton

The Use of Weather, Water, Ice, and Climate (WWIC) Information in the Polar Regions: What Is Known after the Decadelong Polar Prediction Project? - Heinrich, Victoria J.; Stewart, Emma J.; Liggett, Daniela; Carrasco, Jorge F.; Dawson, Jackie; Lamers, Machiel; Ljubicic, Gita J.; Jeuring, Jelmer; Thoman, Rick (Weather, Climate, and Society, 2024)
The polar regions are facing a wide range of compounding challenges, from climate change to increased human activity. Infrastructure, rescue services, and disaster response capabilities are limited in these remote environments. Relevant and usable weather, water, ice, and climate (WWIC) information is vital for safety, activity success, adaptation, and environmental protection. This has been a key focus for the World Meteorological Organization’s (WMO) Polar Prediction Project (PPP), and in particular its “Societal and Economic Research and Applications” (PPP-SERA) Task Team, which together over a decade have sought to understand polar WWIC information use in relation to operational needs, constraints, and decision contexts to inform the development of relevant services. To understand research progress and gaps on WWIC information use during the PPP (2013–23), we undertook a systematic bibliometric review of aligned scholarly peer-reviewed journal articles (n = 43), examining collaborations, topics, methods, and regional differences. Themes to emerge included activity and context, human factors, information needs, situational awareness, experience, local and Indigenous knowledge, and sharing of information. We observed an uneven representation of disciplinary backgrounds, geographic locations, research topics, and sectoral foci. Our review signifies an overall lack of Antarctic WWIC services research and a dominant focus on Arctic sea ice operations and risks. We noted with concern a mismatch between user needs and services provided. Our findings can help to improve WWIC services’ dissemination, communication effectiveness, and actionable knowledge provision for users and guide future research as the critical need for salient weather services across the polar regions remains beyond the PPP. Significance Statement Every day, people in the Arctic and Antarctic use weather, water, ice, and climate information to plan and carry out outdoor activities and operations in a safe way. Despite advances in numerical weather prediction, technology, and product development, barriers to accessing and effectively communicating high-quality usable observations, forecasts, and actionable knowledge remain. Poorer services, prediction accuracy, and interpretation are exacerbated by a lack of integrated social science research on relevant topics and a mismatch between the services provided and user needs. As a result, continued user engagement, research focusing on information use, risk communication, decision-making processes, and the application of science for services remain highly relevant to reducing risks and improving safety for people living, visiting, and working in the polar regions.
Place: Boston MA, USA Publisher: American Meteorological Society
Keywords: Antarktis; klimaendringer; klimatologi; meteorologi; polarområdene

Arctic copepod copper sensitivity and comparison with Antarctic and temperate copepods - Heuschele, Jan; Dinh, Khuong V.; Lode, Torben; Jager, Tjalling; Borgå, Katrine (Ecotoxicology, 2024)
The ongoing global climate crisis increases temperatures in polar regions faster and with greater magnitude than elsewhere. The decline of Arctic sea ice opens up new passages, eventually leading to higher anthropogenic activities such as shipping, fishing, and mining. Climate change and anthropogenic activities will increase contaminant transport from temperate to Arctic regions. The shipping industry uses copper as an antifouling coating. Copper is an essential element but becomes toxic at excess concentrations, and its use may inadvertently affect non-target organisms such as copepods. Copper affects copepods by lowering reproductive output, prolonging developmental time, and causing increased mortality. As data on copper sensitivity of polar copepods at low temperatures are rare, we conducted onboard survival experiments with the Arctic region’s most common copepod species (Calanus finmarchicus, C. glacialis, C. hyperboreus). Acute survival tests were done for up to 8 days on individuals in 70 ml bottles at 1 °C with nominal copper concentrations ranging from 3 to 480 μg L−1. We used a reduced General Unified Threshold model for Survival (GUTS) to analyse the data, and placed our results in the context of the few published copper sensitivity data of the Antarctic and temperate copepod species at low temperatures. The sensitivity of Cu exposure was similar between the three Calanus species. However, a model comparison suggests that the tested C. glacialis population is less sensitive than the other two species in our experiments. Compared to published data, the three Arctic species appear slightly less sensitive to copper compared to their Antarctic counterparts but more compared to their temperate ones. Our literature search revealed only a few available studies on the copper sensitivity of polar copepods. In the future, this species group will be exposed to more pollutants, which warrants more studies to predict potential risks, especially given possible interactions with environmental factors.
Keywords: Antarktis; copepoder; forurensning; hoppekreps; klimaendringer; marin biologi; miljøgifter; polarområdene; økotoksikologi

Ocean warming as a trigger for irreversible retreat of the Antarctic ice sheet - Hill, Emily A.; Gudmundsson, G. Hilmar; Chandler, David M. (Nature Climate Change, 2024)
Warmer ocean conditions could impact future ice loss from Antarctica due to their ability to thin and reduce the buttressing of laterally confined ice shelves. Previous studies highlight the potential for a cold to warm ocean regime shift within the sub-shelf cavities of the two largest Antarctic ice shelves—the Filchner–Ronne and Ross. However, how this impacts upstream ice flow and mass loss has not been quantified. Here using an ice sheet model and an ensemble of ocean-circulation model sub-shelf melt rates, we show that transition to a warm state in those ice shelf cavities leads to a destabilization and irreversible grounding line retreat in some locations. Once this ocean shift takes place, ice loss from the Filchner–Ronne and Ross catchments is greatly accelerated, and conditions begin to resemble those of the present-day Amundsen Sea sector—responsible for most current observed Antarctic ice loss—where this thermal shift has already occurred.
Keywords: Amundsenhavet; Antarktis; Sørishavet; global oppvarming; innlandsis; klimaendringer; klimatologi

Stepwise Oligocene–Miocene breakdown of subpolar gyres and strengthening of the Antarctic Circumpolar Current - Hoem, F. S.; van den Broek, K.; López-Quirós, A.; van de Lagemaat, S. H. A.; Bohaty, S. M.; Hillenbrand, C.-D.; Larter, R. D.; van Peer, T. E.; Brinkhuis, H.; Sangiorgi, F.; Bijl, P. K. (J. Micropalaeontol., 2024)
Through the Cenozoic (66–0 Ma), the dominant mode of ocean surface circulation in the Southern Ocean transitioned from two large subpolar gyres to circumpolar circulation with a strong Antarctic Circumpolar Current (ACC) and complex ocean frontal system. Recent investigations in the southern Indian and Pacific oceans show warm Oligocene surface water conditions with weak frontal systems that started to strengthen and migrate northwards during the late Oligocene. However, due to the paucity of sedimentary records and regional challenges with traditional proxy methods, questions remain about the southern Atlantic oceanographic transition from gyral to circumpolar circulation, with associated development of frontal systems and sea ice cover in the Weddell Sea. Our ability to reconstruct past Southern Ocean surface circulation and the dynamic latitudinal positions of the frontal systems has improved over the past decade. Specifically, increased understanding of the modern ecologic affinity of organic-walled dinoflagellate cyst (dinocyst) assemblages from the Southern Ocean has improved reconstructions of distinct past oceanographic conditions (sea surface temperature, salinity, nutrients, and sea ice) using downcore assemblages from marine sediment records. Here we present new late Oligocene to latest Miocene (∼ 26–5 Ma) dinocyst assemblage data from marine sediment cores in the southwestern Atlantic Ocean (International Ocean Discovery Program (IODP) Site U1536, Ocean Drilling Program (ODP) Site 696 and piston cores from Maurice Ewing Bank). We compare these to previously published latest Eocene–latest Miocene (∼ 37–5 Ma) dinocyst assemblage records and sea surface temperature (SST) reconstructions available from the SW Atlantic Ocean in order to reveal oceanographic changes as the Southern Ocean gateways widen and deepen. The observed dinocyst assemblage changes across the latitudes suggest a progressive retraction of the subpolar gyre and southward migration of the subtropical gyre in the Oligocene–early Miocene, with strengthening of frontal systems and progressive cooling since the middle Miocene (∼ 14 Ma). Our data are in line with the timing of the removal of bathymetric and geographic obstructions in the Drake Passage and Tasmanian Gateway regions, which enhanced deep-water throughflow that broke down gyral circulation into the Antarctic circumpolar flow. Although the geographic and temporal coverage of the data is relatively limited, they provide a first insight into the surface oceanographic evolution of the late Cenozoic southern Atlantic Ocean.
Publisher: Copernicus Publications
Keywords: Sørishavet; Sørishavsstrømmen; Weddellhavet; mikropaleontologi; oseanografi

Revisiting Winter Southern Ocean CO2 Uptake Based on CALIPSO Observations - Huang, Hao; Zhang, Ke; Zhang, Zhaoru; Smith Jr., Walker; He, Jianfeng; Liu, Na; Le, Chengfeng (Geophysical Research Letters, 2024)
The absorption of atmospheric carbon dioxide (CO2) in the Southern Ocean represents a critical component of the global oceanic carbon budget. Previous assessments of air-sea carbon flux variations and long-term trends in polar regions during winter have faced limitations due to scarce field data and the lack of ocean color satellite imagery, causing uncertainties in estimating CO2 flux estimation. This study utilized the Cloud-Aerosol Lidar and Infrared Pathfinder Satellite Observation satellite to construct a continuous 16-year (2006?2021) time series of sea surface partial pressure of CO2 (pCO2) in the Southern Ocean. Our findings revealed that the polar region in South Ocean acts as a carbon sink in winter, with CO2 flux of ?30 TgC in high-latitude areas (South of 50°S). This work highlights the efficacy of active remote sensing for monitoring sea surface pCO2 and contributes insights into the dynamic carbonate systems of the Southern Ocean.
Publisher: John Wiley & Sons, Ltd Article Number: e2024GL108335
Keywords: Sørishavet; karbon syklus; karbondioksid; klimaendringer; oseanografi

Sensitivity of the stock assessment for the Antarctic krill fishery to time-varying natural and fishing mortality - Johannessen, Elling Deehr; Krafft, Bjørn A.; Donovan, Carl R.; Wiff, Rodrigo; Caneco, Bruno; Lowther, Andrew (Fisheries Management and Ecology, 2024)
The stock assessment model for the Antarctic krill fishery is a population model operating on daily timesteps, which permits modeling within-year patterns of some population dynamics. We explored the effects of including within-year patterns in natural and fishing mortality on catch limits of krill, by incorporating temporal presence of key predator species and contemporary temporal trends of the fishing fleet. We found that inclusion of within-year variation in natural and fishing mortalities increased catch limits. Fishing mortality had a greater effect than natural mortality despite differences in top-down predation on krill, and potentially increased catch limits by 24% compared to the baseline model. Additionally, the stock assessment model allowed a higher catch limit when fishing was during peak summer months than autumn. Number of days with active fishing was negatively related to precautionary catch limits. Future stock assessments should incorporate contemporary spatiotemporal fishing trends and consider implementing additional ecosystem components into the model.
Publisher: John Wiley & Sons, Ltd
Keywords: Sørishavet; fiskeriforvaltning; krill; marin økologi; marine økosystemer; plankton

SMOS-derived Antarctic thin sea ice thickness: data description and validation in the Weddell Sea - Kaleschke, L.; Tian-Kunze, X.; Hendricks, S.; Ricker, R. (Earth Syst. Sci. Data, 2024)
Accurate satellite measurements of the thickness of Antarctic sea ice are urgently needed but pose a particular challenge. The Antarctic data presented here were produced using a method to derive the sea ice thickness from 1.4 GHz brightness temperatures previously developed for the Arctic, with only modified auxiliary data. The ability to observe the thickness of thin sea ice using this method is limited to cold conditions, meaning it is only reasonable during the freezing period, typically March to October. The Soil Moisture and Ocean Salinity (SMOS) level-3 sea ice thickness product contains estimates of the sea ice thickness and its uncertainty up to a thickness of about 1 m. The sea ice thickness is provided as a daily average on a polar stereographic projection grid with a sample resolution of 12.5 km, while the SMOS brightness temperature data used have a footprint size of about 35–40 km in diameter. Data from SMOS have been available since 2010, and the mission's operation has been extended to continue until at least the end of 2025. Here we compare two versions of the SMOS Antarctic sea ice thickness product which are based on different level-1 input data (v3.2 based on SMOS L1C v620 and v3.3 based on SMOS L1C 724). A validation is performed to generate a first baseline reference for future improvements of the retrieval algorithm and synergies with other sensors. Sea ice thickness measurements to validate the SMOS product are particularly rare in Antarctica, especially during the winter season and for the valid range of thicknesses. From the available validation measurements, we selected datasets from the Weddell Sea that have varying degrees of representativeness: Helicopter-based EM Bird (HEM), Surface and Under-Ice Trawl (SUIT), and stationary Upward-Looking Sonars (ULS). While the helicopter can measure hundreds of kilometres, SUIT's use is limited to distances of a few kilometres and thus only captures a small fraction of an SMOS footprint. Compared to SMOS, the ULS are point measurements and multi-year time series are necessary to enable a statistically representative comparison. Only four of the ULS moorings have a temporal overlap with SMOS in the year 2010. Based on selected averaged HEM flights and monthly ULS climatologies, we find a small mean difference (bias) of less than 10 cm and a root mean square deviation of about 20 cm with a correlation coefficient R > 0.9 for the valid sea ice thickness range between 0 and about 1 m. The SMOS sea ice thickness showed an underestimate of about 40 cm with respect to the less representative SUIT validation data in the marginal ice zone. Compared with sea ice thickness outside the valid range, we find that SMOS strongly underestimates the real values, which underlines the need for combination with other sensors such as altimeters. In summary, the overall validity of the SMOS sea ice thickness for thin sea ice up to a thickness of about 1 m has been demonstrated through validation with multiple datasets. To ensure the quality of the SMOS product, an independent regional sea ice extent index was used for control. We found that the new version, v3.3, is slightly improved in terms of completeness, indicating fewer missing data. However, it is worth noting that the general characteristics of both datasets are very similar, also with the same limitations.
Publisher: Copernicus Publications
Keywords: Sørishavet; Weddellhavet; havis; klimatologi; meteorologi; sjøis

Radar internal reflection horizons from multisystem data reflect ice dynamic and surface accumulation history along the Princess Ragnhild Coast, Dronning Maud Land, East Antarctica - Koch, Inka; Drews, Reinhard; Franke, Steven; Jansen, Daniela; Oraschewski, Falk Marius; Muhle, Leah Sophie; Višnjević, Vjeran; Matsuoka, Kenichi; Pattyn, Frank; Eisen, Olaf (Journal of Glaciology, 2024)
Ice shelves, which regulate ice flow from the Antarctic ice sheet towards the ocean, are shaped by spatiotemporal patterns of surface accumulation, surface/basal melt and ice dynamics. Therefore, an ice dynamic and accumulation history are imprinted in the internal ice stratigraphy, which can be imaged by radar in the form of internal reflection horizons (IRHs). Here, IRHs were derived from radar data combined across radar platforms (airborne and ground-based) in coastal eastern Dronning Maud Land (East Antarctica), comprising three ice rises and adjacent two ice shelves. To facilitate interpretation of dominant spatiotemporal patterns of processes shaping the local IRH geometry, traced IRHs are classified into three different types (laterally continuous, discontinuous or absent/IRH-free). Near-surface laterally continuous IRHs reveal local accumulation patterns, reflecting the mean easterly wind direction, and correlate with surface slopes. Areas of current and past increased ice flow and internal deformation are marked by discontinuous or IRH-free zones, and can inform about paleo ice-stream dynamics. The established IRH datasets extend continent-wide mapping efforts of IRHs to an important and climatically sensitive ice marginal region of Antarctica and are ready for integration into ice-flow models to improve predictions of Antarctic ice drainage.
Edition: 2023/12/12 Publisher: Cambridge University Press
Keywords: Dronning Maud Land; Sørishavet; glasiologi; isshelf; teknologi

Permafrost and ground-ice conditions in the Untersee Oasis, Queen Maud Land, East Antarctica - Lacelle, Denis; Verret, Marjolaine; Faucher, Benoit; Fisher, David; Gaudreau, Adam; Pellerin, André; Ecclestone, Miles; Andersen, Dale T. (Antarctic Science, 2024)
Knowledge of Antarctic permafrost is mainly derived from the Antarctic Peninsula and Victoria Land. This study examines the 2019–2023 temperature and humidity conditions, distribution and development of polygonal terrain and the origin of ground ice in soils of the Untersee Oasis. In this region, the surface offset (MAAT ≅ MAGST) and the thermal offset (MAGST ≤ TTIT) reflect the lack of vegetation, absence of persistent snow and a dry soil above the ice table. The mean annual vapour pressure at the ground surface is approximately ~2× higher than in the air but is ~0.67× lower than at the ice table. The size of polygons appears to be in equilibrium with the ice-table depth, and numerical modelling suggests that the depth of the ice table is in turn in equilibrium with the ground surface temperature and humidity. The ground ice at the ice table probably originates from the partial evaporation of snowmelt that infiltrated the dry soil column. As such, the depth of the ice table in this region is set by the water vapour density gradient between the ground surface and the ice-bearing ground, but it is recharged periodically by evaporating snowmelt.
Edition: 2024/12/17 Publisher: Cambridge University Press
Keywords: Dronning Maud Land; fysisk geografi; geologi; permafrost

Hydrography and circulation below Fimbulisen Ice Shelf, East Antarctica, from 14 years of moored observations - Lauber, Julius; Hattermann, Tore; de Steur, Laura; Darelius, Elin; Fransson, Agneta (Ocean Sci., 2024)
Future mass loss from the East Antarctic Ice Sheet represents a major uncertainty in projections of future sea level rise. Recent studies have highlighted the potential vulnerability of the East Antarctic Ice Sheet to atmospheric and oceanic changes, but long-term observations inside the ice shelf cavities are rare. Here, we present new insights from observations from three oceanic moorings below Fimbulisen Ice Shelf from 2009 to 2023. We examine the characteristics of intrusions of modified Warm Deep Water (mWDW) across a sill connecting the cavity to the open ocean and investigate seasonal variability of the circulation and water masses inside the cavity using an optimum multiparameter analysis. In autumn, the water below the 345 m deep central part of the ice shelf is composed of up to 30 % solar-heated, buoyant Antarctic Surface Water (ASW), separating colder Ice Shelf Water from the ice base and affecting the cavity circulation on seasonal timescales. At depth, the occurrence of mWDW is associated with the advection of cyclonic eddies across the sill into the cavity. These eddies reach up to the ice base. The warm intrusions are observed most often from January to March and from September to November, and traces of mWDW-derived meltwater close to the ice base imply an overturning of these warm intrusions inside the cavity. We suggest that this timing is set by both the offshore thermocline depth and the interactions of the Antarctic Slope Current with the ice shelf topography over the continental slope. Our findings provide a better understanding of the interplay between shallow inflows of ASW contributions and deep inflows of mWDW for basal melting at Fimbulisen Ice Shelf, with implications for the potential vulnerability of the ice shelf to climate change.
Publisher: Copernicus Publications
Keywords: Dronning Maud Land; hydrografi; isshelf; klimaendringer; klimatologi; oseanografi

ALBATROSS: Advancing Southern Ocean tide modelling with high resolution and enhanced bathymetry - Le Merle, Eva; Belot, Carole; Fouchet, Ergane; Cancet, Mathilde; Andersen, Ole Baltazar; Lyard, Florent; Moholdt, Geir; Tsamados, Michel; El Hajj, Mahmoud; Maton, Josephine; Benveniste, Jérôme; Restano, Marco (Polar Science, 2024)
The knowledge of bathymetry and ocean tides plays a pivotal role at the crossroads of various scientific fields, especially in the Polar regions. Its significance extends to ocean circulation modeling and understanding the coupled dynamical response of the ocean, sea-ice and ice-sheet systems. In the Southern Ocean, conventional satellite altimetry measurements are rare below the 66° parallel. Hydrodynamic models are thus useful tools to provide spatially continuous information about ocean tides. However, the accuracy of ocean tide models around the Antarctic continent is currently limited by the quality of bathymetry. Recent reprocessing of decade-long CryoSat-2 data has facilitated a new computation of bathymetry around Antarctica, bringing innovative information on bathymetry gradients. This, combined with new compilations of bathymetry, ice draft, coastline, and grounding line datasets in ice-shelf regions, allows improving models and knowledge of ocean tides in the Southern Ocean. We developed a new high-resolution tidal model that implements the improved bathymetry data and includes data assimilation of satellite-altimetry tidal retrievals computed from CryoSat-2, filling the gap between the 66°S-limited coverage of the TOPEX-Jason suite missions and the Antarctic coast. Comparisons with tidal estimates derived from tide gauge measurements showed very good consistencies with an RMSE of 3 cm.
Article number: 101124
Keywords: Sørishavet; batymetri; geofysikk

Phytoplankton bloom distribution and succession driven by sea-ice melt in the Kong Håkon VII Hav - Lenss, Megan; Moreau, Sebastien; Hattermann, Tore; Wiktor, Jozef; Różańska, Magdalena; Claeys, Philippe; Brion, Natacha; Chierici, Melissa; Fransson, Agneta; Campbell, Karley (Elementa: Science of the Anthropocene, 2024)
The existence of ice-edge phytoplankton blooms in the Southern Ocean is well described, yet direct observations of the mechanisms of phytoplankton bloom development following seasonal sea-ice melt remain scarce. This study constrains such responses using biological and biogeochemical datasets collected along a coastal-to-offshore transect that bisects the receding sea-ice zone in the Kong Håkon VII Hav (off the coast of Dronning Maud Land). We documented that the biogeochemical growing conditions for phytoplankton vary on a latitudinal gradient of sea-ice concentration, where increased sea-ice melting creates optimal conditions for growth with increased light availability and potentially increased iron supply. The zones of the study area with the least ice cover were associated with diatom dominance, the greatest chlorophyll a concentrations, net community production, and dissolved inorganic carbon drawdown, as well as lower sea surface fugacity of CO2. Together, these associations imply higher potential for an oceanic CO2 sink due, at least in part, to more advanced bloom phase and/or larger bloom magnitude stemming from a relatively longer period of light exposure, as compared to the more ice-covered zones in the study area. From stable oxygen isotope fractions, sea-ice meltwater fractions were highest in the open ocean zone and meteoric meltwater fractions were highest in the coastal and polynya zones, suggesting that potential iron sources may also change on a latitudinal gradient across the study area. Variable phytoplankton community compositions were related to changing sea-ice concentrations, with a typical species succession from sympagic flagellate species (Pyramimonas sp. and Phaeocystis antarctica) to pelagic diatoms (e.g., Dactyliosolen tenuijunctus) observed across the study area. These results fill a spatiotemporal gap in the Southern Ocean, as sea-ice melting plays a larger role in governing phytoplankton bloom dynamics in the future Southern Ocean due to changing sea-ice conditions caused by anthropogenic global warming.
Article Number: 00122
Keywords: Sørishavet; biogeokjemi; fytoplankton; havis; oseanografi; sjøis

Diversity, toxicity, and distribution of potentially toxic diatoms in Antarctic waters––With description of Pseudo-nitzschia meridionalis sp. nov. and P. glacialis sp. nov. - Lundholm, Nina; Christensen, Anneliese L.; Olesen, Anna K.J.; Beszteri, Bánk; Eggers, Sarah Lena; Krock, Bernd; Altenburger, Andreas (Harmful Algae, 2024)
Diatoms of the genus Pseudo-nitzschia, known for their potential toxicity, are integral to the phytoplankton community of the Southern Ocean, which surrounds Antarctica. Despite their ecological importance, the diversity and toxicity of Pseudo-nitzschia in this region remain underexplored. Globally, these diatoms are notorious for forming harmful algal blooms in temperate and tropical waters, causing significant impacts on marine life, ecosystems, and coastal economies. However, detailed information on the diversity, morphology, and toxicity of Pseudo-nitzschia species in Antarctic waters is limited, with molecular characterizations of these species being particularly scarce. During three research expeditions to the Southern Ocean, monoclonal strains of Pseudo-nitzschia were isolated and cultivated. Stored samples from a fourth expedition, the Brategg expedition, were used to complete the description of particularly P. turgidula. Through electron microscopy and molecular analysis, two novel species were identified—Pseudo-nitzschia meridionalis sp. nov. and Pseudo-nitzschia glacialis sp. nov.—alongside the previously described species P. subcurvata, P. turgiduloides, and P. turgidula. Toxin assays revealed no detectable levels of domoic acid in P. turgiduloides, P. turgidula, P. meridionalis sp. nov. and P. glacialis sp. nov. Conversely, P. subcurvata was reported in a related study to produce domoic acid and its isomer, isodomoic acid C. These findings emphasize the need for comprehensive research on the phytoplankton of Antarctic waters, which is currently a largely uncharted domain. With the looming threat of climate change, understanding the dynamics of potentially harmful algal populations in this region is becoming increasingly critical.
Article Number: 102724
Keywords: Rosshavet; Sørishavet; alger; biodiversitet; diatomeer; fytoplankton; marin biologi

Supraglacial lake evolution and its drivers in Dronning Maud Land, East Antarctica - Mahagaonkar, Anirudha; Moholdt, Geir; Glaude, Quentin; Schuler, Thomas Vikhamar (Journal of Glaciology, 2024)
Supraglacial lakes on Antarctic ice shelves can have far-reaching implications for ice-sheet stability, highlighting the need to understand their dynamics, controls and role in the ice-sheet mass budget. We combine a detailed satellite-based record of seasonal lake evolution in Dronning Maud Land with a high-resolution simulation from the regional climate model Modèle Atmosphérique Régional to identify drivers of lake variability between 2014 and 2021. Correlations between summer lake extents and climate parameters reveal complex relationships that vary both in space and time. Shortwave radiation contributes positively to the energy budget during summer melt seasons, but summers with enhanced longwave radiation are more prone to surface melting and ponding, which is further enhanced by advected heat from summer precipitation. In contrast, previous winter precipitation has a negative effect on summer lake extents, presumably by increasing albedo and pore space, delaying the accumulation of meltwater. Downslope katabatic or föhn winds promote ponding around the grounding zones of some ice shelves. At a larger scale, we find that summers during periods of negative southern annular mode are associated with increased ponding in Dronning Maud Land. The high variability in seasonal lake extents indicates that these ice shelves are highly sensitive to future warming or intensified extreme events.
Edition: 2024/10/02 Publisher: Cambridge University Press
Keywords: Dronning Maud Land; fjernmåling; glasiologi; innlandsis; isshelf; klimamodeller; subglasial innsjø

The case for a Framework for UnderStanding Ice-Ocean iNteractions (FUSION) in the Antarctic-Southern Ocean system - McCormack, Felicity S.; Cook, Sue; Goldberg, Daniel N.; Nakayama, Yoshihiro; Seroussi, Hélène; Nias, Isabel; An, Lu; Slater, Donald; Hattermann, Tore (Elementa: Science of the Anthropocene, 2024)
We are in a period of rapidly accelerating change across the Antarctic continent and Southern Ocean, with land ice loss leading to sea level rise and multiple other climate impacts. The ice-ocean interactions that dominate the current ice loss signal are a key underdeveloped area of knowledge. The paucity of direct and continuous observations leads to high uncertainty in the glaciological, oceanographic and atmospheric fields required to constrain ice-ocean interactions, and there is a lack of standardised protocols for reconciling observations across different platforms and technologies and modelled outputs. Funding to support observational campaigns is under increasing pressure, including for long-term, internationally coordinated monitoring plans for the Antarctic continent and Southern Ocean. In this Practice Bridge article, we outline research priorities highlighted by the international ice-ocean community and propose the development of a Framework for UnderStanding Ice-Ocean iNteractions (FUSION), using a combined observational-modelling approach, to address these issues. Finally, we propose an implementation plan for putting FUSION into practice by focusing first on an essential variable in ice-ocean interactions: ocean-driven ice shelf melt.
Article number: 00036
Keywords: Antarktis; Sørishavet; glasiologi; innlandsis; klimamodeller; klimatologi; oseanografi

Miocene ice sheet dynamics and sediment deposition in the central Ross Sea, Antarctica - McKay, Robert; Cockrell, Jay; Shevenell, Amelia E.; Laberg, Jan Sverre; Burns, Julianne; Patterson, Molly; Kim, Sunghan; Naish, Tim; Harwood, David; Levy, Richard; Marschalek, James; van de Flierdt, Tina; et al. (GSA Bulletin, 2024)
Drill cores from the Antarctic continental shelf are essential for directly constraining changes in past Antarctic Ice Sheet extent. Here, we provide a sedimentary facies analysis of drill cores from International Ocean Discovery Program (IODP) Site U1521 in the Ross Sea, which reveals a unique, detailed snapshot of Antarctic Ice Sheet evolution between ca. 18 Ma and 13 Ma. We identify distinct depositional packages, each of which contains facies successions that are reflective of past baseline shifts in the presence or absence of marine-terminating ice sheets on the outermost Ross Sea continental shelf. The oldest depositional package (>18 Ma) contains massive diamictites stacked through aggradation and deposited in a deep, actively subsiding basin that restricted marine ice sheet expansion on the outer continental shelf. A slowdown in tectonic subsidence after 17.8 Ma led to the deposition of progradational massive diamictites with thin mudstone beds/laminae, as several large marine-based ice sheet advances expanded onto the mid- to outer continental shelf between 17.8 Ma and 17.4 Ma. Between 17.2 Ma and 15.95 Ma, packages of interbedded diamictite and diatom-rich mudstone were deposited during a phase of highly variable Antarctic Ice Sheet extent and volume. This included periods of Antarctic Ice Sheet advance near the outer shelf during the early Miocene Climate Optimum (MCO)—despite this being a well-known period of peak global warmth between ca. 17.0 Ma and 14.6 Ma. Conversely, there were periods of peak warmth within the MCO during which diatom-rich mudstones with little to no ice-rafted debris were deposited, which indicates that the Antarctic Ice Sheet was greatly reduced in extent and had retreated to a smaller terrestrial-terminating ice sheet, most notably between 16.3 Ma and 15.95 Ma. Post-14.2 Ma, diamictites and diatomites contain unambiguous evidence of subglacial shearing in the core and provide the first direct, well-dated evidence of highly erosive marine ice sheets on the outermost continental shelf during the onset of the Middle Miocene Climate Transition (MMCT; 14.2–13.6 Ma). Although global climate forcings and feedbacks influenced Antarctic Ice Sheet advances and retreats during the MCO and MMCT, we propose that this response was nonlinear and heavily influenced by regional feedbacks related to the shoaling of the continental shelf due to reduced subsidence, sediment infilling, and local sea-level changes that directly influenced oceanic influences on melting at the Antarctic Ice Sheet margin. Although intervals of diatom-rich muds and diatomite indicating open-marine interglacial conditions still occurred during (and following) the MMCT, repeated advances of marine-based ice sheets since that time have resulted in widespread erosion and overdeepening in the inner Ross Sea, which has greatly enhanced sensitivity to marine ice sheet instability since 14.2 Ma.
Keywords: Rosshavet; Sørishavet; geologi; oseanografi; paleoklimatologi

KRILLSCAN: An automated open-source software for processing and analysis of echosounder data from the Antarctic krill fishery - Menze, Sebastian; Macaulay, Gavin J.; Zhang, Guosong; Lowther, Andrew D.; Krafft, Bjørn A. (Fisheries Management and Ecology, 2024)
Krillscan software was developed to automatically process echosounder data and achieve an accelerated and transparent analysis of backscatter data that allows calculation of target biomass. Herein, the fishery for Antarctic krill (Euphausia superba, Henceforth Krill) was used as a case study to develop the approach. Implementation of a sustainable management strategy for the krill fishery is complicated by a lack of regularly updated krill abundance data on spatiotemporal scales of the fishery. To increase krill biomass data availability, automatic echosounder data processing and swarm detection software was tested against traditional manual scrutinization with LSSS software and agreed with only minor offsets in estimated nautical area scattering coefficients. In addition to automatic processing and data transfer, Krillscan also has a graphical user interface to supervise automatic krill swarm detection. Echogram size can be compressed up to 100 times and raw data are processed faster than generated, thereby enabling near-real time analysis and data transfer. Compressed data can be transmitted online to allow fishing vessels to conduct surveys without having scientific personnel with special expertise on board.
Publisher: John Wiley & Sons, Ltd Article number: e12739
Keywords: Sørishavet; dataanalyse; ekkolodd; fiskerier; krill; plankton

Antarctic sonobuoy surveys for blue whales from 2006-2021 reveal contemporary distribution, changes over time, and paths to further our understanding of their distribution and biology - Miller, Brian S.; Andrews-Goff, Virginia; Barlow, Jay; Bell, Elanor; Calderan, Susannah; Double, Michael C.; Gedamke, Jason; Kelly, Nat; Laverick, Sarah; Leaper, Russell; Miller, Elanor J.; Reeve, Kym; et al. (Frontiers in Marine Science, 2024)
Seven passive acoustic surveys for marine mammal sounds were conducted by deploying sonobuoys along ship tracks during Antarctic voyages spanning years 2006-2021. These surveys included nearly 330° of longitude throughout Antarctic (south of 60°S) and sub-Antarctic (between 50-60°S) latitudes. Here, we summarise the presence of calls from critically endangered Antarctic blue whales (Balaenoptera musculus intermedia) detected on all seven of these surveys. We describe and compare the spatial distribution of detections of three different types of Antarctic blue whale calls: unit-A, Z-calls, and D-calls. Three sets of voyages partially overlapped spatially but in different years, providing three regions (Indian Sector, Dumont d’Urville Sea, Ross Sea) to investigate differences over time for these three different call types. The proportion of sonobuoys with calls present was significantly higher in the more recent years for seven of the 15 combinations of years, regions, and call type. The proportion of sonobuoys with calls present was significantly lower only for one of the 15 combinations (unit A in the Ross Sea between 2015 vs 2017), and not significantly different for the remaining seven pairwise comparisons. We discuss possible explanations for these observations including: differences in probability of detection, whale behaviour, whale distribution, and abundance. These explanations are not mutually exclusive and cannot yet be resolved without application of complex analytical methods and collection of additional data. Lastly, we discuss future work that could help clarify the contributions of each of these potential drivers of acoustic detection. We propose continued acoustic data collection, application of new analytical methods, and collection of other synergistic data from Antarctic blue whales on their feeding grounds as a basis for future work on this species. This could provide a cost effective and holistic means of monitoring their status after the effects of 20th century industrial whaling, as well as their responses to natural and anthropogenic changes to their main prey, Antarctic krill, and a changing climate.
Keywords: Sørishavet; hvaler; hydroakustikk; marin biologi

Antarctic Blue Ice Areas are hydrologically active, nutrient rich and contain microbially diverse cryoconite holes - Nowak, Aga; Isaksson, Elisabeth; Sunde, Øyvind; Elvevold, Synnøve; Sandven, Håkon; Moholdt, Geir; Hudson, Stephen R.; Urset, Anne; Edwards, Arwyn; Rassner, Sara M. E.; Pearce, David; Hamre, Børge; et al. (Communications Earth & Environment, 2024)
Antarctica is the coldest, windiest and least inhabited place on Earth. One of its most enigmatic regions is scoured by katabatic winds blue ice that covers 235,000 km2 of the Antarctic fringe. Here, we demonstrate that contrary to common belief, high-altitude inland blue ice areas are not dry, nor barren. Instead, they promote sub-surface melting that enables them to become “powerplants” for water, nutrients, carbon and major ions production. Mapping cryoconite holes at an unprecedented scale of 62 km2 also revealed a regionally significant resource of dissolved nitrogen, phosphorus (420 kg km−2), dissolved carbon (1323 kg km−2), and major ions (6672 kg km−2). We discovered that unlike on glaciers, creation of cryoconite holes and their chemical signature on the ice sheet is governed by ice movement and bedrock geology. Blue ice areas are near-surface hotspots of microbial life within cryoconite holes. Bacterial communities they support are unexpectedly diverse. We also show that near-surface aquifers can exist in blue ice outside cryoconite holes. Identifying blue ice areas as active ice sheet ecosystems will help us understand the role ice sheets play in Antarctic carbon cycle, development of near-surface drainage system, and will expand our perception of the limits of life.
Keywords: Antarktis; biogeokjemi; geografi; geologi; mikrobielle organismer; mikrobiologi

The Troll Observing Network (TONe): A contribution to improving observations in the data-sparse region of Dronning Maud Land, Antarctica - Pedersen, Christina A.; Njåstad, Birgit; Aas, Wenche; Darelius, Elin; Descamps, Sébastien; Flått, Stig; Hattermann, Tore; Hudson, Stephen R.; Miloch, Wojciech J.; Rykkje, Simen; Schweitzer, Johannes; Storvold, Rune; et al. (Polar Research, 2024)
Understanding how Antarctica is changing and how these changes influence the rest of the Earth is fundamental to the future robustness of human society. Strengthening our understanding of these changes and their implications requires dedicated, sustained and coordinated observations of key Antarctic indicators. The Troll Observing Network (TONe), now under development, is Norway’s contribution to the global need for sustained, coordinated, complementary and societally relevant observations from Antarctica. When fully implemented within the coming three years, TONe will be a state-of-the-art, multi-platform, multi-disciplinary observing network in data-sparse Dronning Maud Land. A critical part of the network is a data management system that will ensure broad, free access to all TONe data to the international research community.
Section: Perspectives
Keywords: Antarktis; Dronning Maud Land; Sørishavet; Troll forskningsstasjon; biologi; datainnsamling; forskningsinfrastruktur; fysikk; geologi; internasjonal samarbeid; kjemi

TerrANTALife 1.0 Biodiversity data checklist of known Antarctic terrestrial and freshwater life forms - Pertierra, Luis R.; Varliero, Gilda; Barbosa, Andrés; Biersma, Elisabeth M.; Convey, Peter; Chown, Steven L.; Cowan, Don; De Los Rios, Asunción; Escribano-Alvarez, Pablo; Fontaneto, Diego; Fraser, Ceridwen; Harris, Mathew; et al. (Biodiversity Data Journal, 2024)
Incomplete species inventories for Antarctica represent a key challenge for comprehensive ecological research and conservation in the region. Additionally, data required to understand population dynamics, rates of evolution, spatial ranges, functional traits, physiological tolerances and species interactions, all of which are fundamental to disentangle the different functional elements of Antarctic biodiversity, are mostly missing. However, much of the fauna, flora and microbiota in the emerged ice-free land of the continent have an uncertain presence and/or unresolved status, with entire biodiversity compendia of prokaryotic groups (e.g. bacteria) being missing. All the available biodiversity information requires consolidation, cross-validation, re-assessment and steady systematic inclusion in order to create a robust catalogue of biodiversity for the continent.We compiled, completed and revised eukaryotic species inventories present in terrestrial and freshwater ecosystems in Antarctica in a new living database: terrANTALife (version 1.0). The database includes the first integration in a compendium for many groups of eukaryotic microorganisms. We also introduce a first catalogue of amplicon sequence variants (ASVs) of prokaryotic biodiversity. Available compendia and literature to date were searched for Antarctic terrestrial and freshwater species, integrated, taxonomically harmonised and curated by experts to create comprehensive checklists of Antarctic organisms. The final inventories comprises 470 animal species (including vertebrates, free-living invertebrates and parasites), 306 plants (including all Viridiplantae: embryophytes and green algae), 997 fungal species and 434 protists (sensu lato). We also provide a first account for many groups of microorganisms, including non-lichenised fungi and multiple groups of eukaryotic unicellular species (Stramenophila, Alveolata and Rhizaria (SAR), Chromists and Amoeba), jointly referred to as "protists". In addition, we identify 1753 bacterial (obtained from 348117 ASVs) and 34 archaeal genera (from 1848 ASVs), as well as, at least, 14 virus families. We formulate a basic tree of life in Antarctica with the main lineages listed in the region and their “known-accepted-species” numbers.
Publisher: Pensoft Publishers
Keywords: Antarktis; Sørishavet; biodiversitet; database; fauna; flora; mikroorganismer

The Late Holocene deglaciation of James Ross Island, Antarctic Peninsula: OSL and 14C-dated multi-proxy sedimentary record from Monolith Lake - Roman, Matěj; Píšková, Anna; Sanderson, David C.W.; Cresswell, Alan J.; Bulínová, Marie; Pokorný, Matěj; Kavan, Jan; Jennings, Stephen J.A.; Lirio, Juan M.; Nedbalová, Linda; Sacherová, Veronika; Kopalová, Kateřina; et al. (Quaternary Science Reviews, 2024)
Lentic waterbodies provide terrestrial sedimentary archives of palaeoenvironmental change in deglaciated areas of the Antarctic. Knowledge of the long-term evolution of Antarctic palaeoenvironments affords important context to the current marked impacts of climate change in the Polar regions. Here, we present a comprehensively dated, multi-proxy sedimentary record from Monolith Lake, a distal proglacial lake in one of the largest ice-free areas of the Antarctic Peninsula region. Of the two defined sedimentary units in the cores studied, the lower Unit 1 exhibits a homogeneous composition and unvarying proxy data profiles, suggesting rapid clastic deposition under uniform, ice-proximal conditions with a sedimentation rate of ∼1 mm yr−1. 14C and optically stimulated luminescence (OSL) dating bracket the deposition interval to 1.5–2.5 ka BP, with the older age being more probable when compared to independent dating of the local deglaciation. The uppermost 11 cm of the record spans the last ∼2.2 ka BP (maximum age), suggesting a markedly decreased sedimentation rate of ∼0.05 mm yr−1 within Unit 2. Whereas Unit 1 shows only scarce evidence of biological activity, Unit 2 provides an uninterrupted record of diatoms (with 29 species recorded) and faunal subfossils, including the fairy shrimp Branchinecta gaini. Concentrations of organically-derived elements, as well as diatoms and faunal remains, are consistent, implying a gradual increase in lake productivity. These results provide an example of long-term Antarctic ‘greening’ (i.e. increasing organic productivity in terrestrial habitats) from a palaeolimnological perspective. The boundary between Units 1 and 2, therefore, marks the timing of local deglaciation at the final stages of a period of negative glacier mass balance, i.e. the Mid-Late Holocene Hypsithermal. Subsequent Neoglacial cooling is evidenced by the abated influence of glacial meltwater streams and turbidity decline linked to reduced glacier runoff, although most proxy responses mirror the natural proglacial lake ontogeny.
Keywords: Antarktis; diatomeer; geografi; geologi; holocene; innsjøer; paleolimnologi; paleoøkologi

Permafrost Hydrogeology of Taylor Valley, Antarctica: Insights From Deep Electrical Resistivity Tomography - Romano, Valentina; Fischanger, Federico; Wilson, Gary; Sciarra, Alessandra; Mazzini, Adriano; Mazzoli, Claudio; Florindo, Fabio; Tartarello, Maria Chiara; Ascani, Massimiliano; Anderson, Jacob; Worthington, Rachel; Hardie, Richard; et al. (Geophysical Research Letters, 2024)
Abstract Global warming has prompted globally widespread permafrost thawing, resulting in enhanced greenhouse gas release into the atmosphere. Studies conducted in the Northern Hemisphere reveal an alarming increase in permafrost thawing. However, similar data from Antarctica are scarce. We conducted a 2-D Deep Electrical Resistivity Tomography (DERT) survey in Taylor Valley, Antarctica, to image the distribution of permafrost, its thicknesses, lower boundaries, and hydrogeology. Results show resistive, discontinuous domains that we suggest represent permafrost units. We also find highly conductive layers (5?10 Ω·m), between 300?350 m and 600?650 m below ground level and a shallower (?50?100 m depth) conductive layer. The combined data set reveals a broad brine system in Taylor Valley, implying multi-tiered groundwater circulation: a shallow, localized system linked with surface water bodies and a separate deeper, regional circulation system. The arrangement of these brines across different levels, coupled with the uneven permafrost distribution, underscores potential interplay between the two systems.
Publisher: John Wiley & Sons, Ltd Article Number: e2023GL106912
Keywords: Antarktis; geologi; global oppvarming; hydrogeologi; klimaendringer; permafrost

Combined physical and biogeochemical assessment of mesoscale eddy parameterisations in ocean models: Eddy-induced advection at eddy-permitting resolutions - Ruan, X.; Couespel, D.; Lévy, M.; Li, J.; Mak, J.; Wang, Y. (Ocean Modelling, 2024)
Ocean general circulation models at the eddy-permitting regime are known to under-resolve the mesoscale eddy activity and associated eddy-mean interaction. Under-resolving the mesoscale eddy field has consequences for the resulting mean state, affecting the modelled ocean circulation and biogeochemical responses, and impacting the quality of climate projections. There is an ongoing debate on whether and how a parameterisation should be utilised in the eddy-permitting regime. Focusing on the Gent–McWilliams (GM) based parameterisations, it is known that, on the one hand, not utilising a parameterisation leads to insufficient eddy feedback and results in biases. On the other hand, utilising a parameterisation leads to double-counting of the eddy feedback, and introduces other biases. A recently proposed approach, known as splitting, modifies the way GM-based schemes are applied in eddy-permitting regimes, and has been demonstrated to be effective in an idealised Southern Ocean channel model. In this work, we evaluate whether the splitting approach can lead to improvements in the physical and biogeochemical responses in an idealised double gyre model. Compared with a high resolution mesoscale eddy resolving model truth, the use of the GM-based GEOMETRIC parameterisation together with splitting in the eddy-permitting regime leads to broad improvements in the control pre-industrial scenario and an idealised climate change scenario, over models with and models without the GM-based GEOMETRIC parameterisation active. While there are still some deficiencies, particularly in the subtropical region where the transport is too weak and may need momentum re-injection to reduce the biases, the present work provides further evidence in support of using the splitting procedure together with a GM-based parameterisation in ocean general circulation models at eddy-permitting resolutions.
Article number: 102396
Keywords: Sørishavet; havstrømmer; klimaendringer; oseanografi

Identifying prey capture events of a free-ranging marine predator using bio-logger data and deep learning - Schoombie, Stefan; Jeantet, Lorène; Chimienti, Marianna; Sutton, Grace J.; Pistorius, Pierre A.; Dufourq, Emmanuel; Lowther, Andrew D.; Oosthuizen, W. Chris (Royal Society Open Science, 2024)
Marine predators are integral to the functioning of marine ecosystems, and their consumption requirements should be integrated into ecosystem-based management policies. However, estimating prey consumption in diving marine predators requires innovative methods as predator-prey interactions are rarely observable. We developed a novel method, validated by animal-borne video, that uses tri-axial acceleration and depth data to quantify prey capture rates in chinstrap penguins (Pygoscelis antarctica). These penguins are important consumers of Antarctic krill (Euphausia superba), a commercially harvested crustacean central to the Southern Ocean food web. We collected a large data set (n = 41 individuals) comprising overlapping video, accelerometer and depth data from foraging penguins. Prey captures were manually identified in videos, and those observations were used in supervised training of two deep learning neural networks (convolutional neural network (CNN) and V-Net). Although the CNN and V-Net architectures and input data pipelines differed, both trained models were able to predict prey captures from new acceleration and depth data (linear regression slope of predictions against video-observed prey captures = 1.13; R2 approximate to 0.86). Our results illustrate that deep learning algorithms offer a means to process the large quantities of data generated by contemporary bio-logging sensors to robustly estimate prey capture events in diving marine predators.
Publisher: Royal Society
Keywords: Sørishavet; biologging; krill; marin biologi; marin zoologi; marine økosystemer; pingviner; plankton

Evolution of the Antarctic Ice Sheet Over the Next Three Centuries From an ISMIP6 Model Ensemble - Seroussi, Hélène; Pelle, Tyler; Lipscomb, William H.; Abe-Ouchi, Ayako; Albrecht, Torsten; Alvarez-Solas, Jorge; Asay-Davis, Xylar; Barre, Jean-Baptiste; Berends, Constantijn J.; Bernales, Jorge; Blasco, Javier; Caillet, Justine; et al. (Earth's Future, 2024)
Abstract The Ice Sheet Model Intercomparison Project for CMIP6 (ISMIP6) is the primary effort of CMIP6 (Coupled Model Intercomparison Project?Phase 6) focusing on ice sheets, designed to provide an ensemble of process-based projections of the ice-sheet contribution to sea-level rise over the twenty-first century. However, the behavior of the Antarctic Ice Sheet beyond 2100 remains largely unknown: several instability mechanisms can develop on longer time scales, potentially destabilizing large parts of Antarctica. Projections of Antarctic Ice Sheet evolution until 2300 are presented here, using an ensemble of 16 ice-flow models and forcing from global climate models. Under high-emission scenarios, the Antarctic sea-level contribution is limited to less than 30 cm sea-level equivalent (SLE) by 2100, but increases rapidly thereafter to reach up to 4.4 m SLE by 2300. Simulations including ice-shelf collapse lead to an additional 1.1 m SLE on average by 2300, and can reach 6.9 m SLE. Widespread retreat is observed on that timescale in most West Antarctic basins, leading to a collapse of large sectors of West Antarctica by 2300 in 30%?40% of the ensemble. While the onset date of retreat varies among ice models, the rate of upstream propagation is highly consistent once retreat begins. Calculations of sea-level contribution including water density corrections lead to an additional ?10% sea level and up to 50% for contributions accounting for bedrock uplift in response to ice loading. Overall, these results highlight large sea-level contributions from Antarctica and suggest that the choice of ice sheet model remains the leading source of uncertainty in multi-century projections.
Publisher: John Wiley & Sons, Ltd
Keywords: Antarktis; geovitenskap; glasiologi; innlandsis; klimamodeller

Observed Pathways and Interannual Variability of the Warm Inflow Onto the Continental Shelf in the Southern Weddell Sea - Steiger, N.; Sallée, J. B.; Darelius, Elin; Janout, Markus; Østerhus, Svein (Journal of Geophysical Research: Oceans, 2024)
Model projections suggest that the continental shelf in the southern Weddell Sea may experience a shift from today's near-freezing temperature to a much warmer state, where warm water floods the shelf and basal melt rates beneath the Filchner Ronne Ice Shelf increase dramatically. Today, the Filchner Trough serves as a conduit for the southward flow of Warm Deep Water (WDW) during summer and, thus, requires continuous monitoring of its hydrographic conditions. An extensive network of moorings was installed at key sites along the inflow pathway from 2017 to 2021, to expand on existing mooring records starting in 2014. The moorings complemented with under-ice profiling floats reveal two inflow pathways, where WDW enters along the eastern flank of the Filchner Trough as well as through a smaller trough east of there. Within the observed period, 2017 and 2018 feature anomalously warm inflows. The inflow is regulated by the heaving of isopycnals over the continental slope, and the southward propagation toward Filchner Ice Shelf is two times faster during these warm years. Furthermore, the warm years coincide with low summer sea ice concentration, which enhances surface stratification through increased freshwater input and modifies sea ice-ocean stresses that both act to lift the warm water layer and increase the temperatures on the continental shelf. Finally, the recent record low sea ice conditions around the Antarctic emphasize the importance of our findings and raise concerns regarding a potentially increasing presence of WDW on the southern Weddell Sea shelf.
Publisher: John Wiley & Sons, Ltd
Keywords: Sørishavet; Weddellhavet; havis; isshelf; oseanografi; sjøis

The Southern Ocean sea-ice ecosystem is important to humans - Steiner, Nadja; Eronen-Rasimus, Eeva; Falardeau, Marianne; Moreau, Sebastien; Steiner, Finn (Frontiers for young minds, 2024)
Did you know that ecosystems support the wellbeing of humans by simply existing? An ecosystem describes the living things in an area, their interactions, and their environment. The ways that ecosystems benefit the wellbeing of humans are called ecosystem services. There are several types of ecosystem services: supporting (they support animals and their homes), provisioning (they provide food and other materials), cultural (they support our hobbies and cultural activities, such as tourism and arts), or regulating (they regulate our climate, for example by taking up carbon dioxide). Understanding the importance of an ecosystem through its ecosystem services helps guide decisions regarding the environment, such as how much fishing or ship traffic should be allowed in an area, or if an area or species should be protected. In this article, we describe the specific ecosystem services of the sea ice and Southern Ocean around Antarctica.
Article number : 1046644
Keywords: Sørishavet; havis; marine økosystemer; populærvitenskap; sjøis; økosystemer

Suppression of Mesoscale Eddy Mixing by Topographic PV Gradients - Sterl, Miriam F.; LaCasce, Joseph H.; Groeskamp, Sjoerd; Nummelin, Aleksi; Isachsen, Pål E.; Baatsen, Michiel L. J. (Journal of Physical Oceanography, 2024)
Oceanic mesoscale eddy mixing plays a crucial role in Earth’s climate system by redistributing heat, salt, and carbon. For many ocean and climate models, mesoscale eddies still need to be parameterized. This is often done via an eddy diffusivity K , which sets the strength of turbulent downgradient tracer fluxes. A well-known effect is the modulation of K in the presence of background potential vorticity (PV) gradients, which suppresses cross-PV gradient mixing. Topographic slopes can induce such suppression through topographic PV gradients. However, this effect has received little attention, and topographic effects are often not included in parameterizations for K . In this study, we show that it is possible to describe the effect of topography on K analytically in a barotropic framework, using a simple stochastic representation of eddy–eddy interactions. We obtain an analytical expression for the depth-averaged K as a function of the bottom slope, which we validate against diagnosed eddy diffusivities from a numerical model. The obtained analytical expression can be generalized to any constant barotropic PV gradient. Moreover, the expression is consistent with empirical parameterizations for eddy diffusivity over topography from previous studies and provides a physical rationalization for these parameterizations. The new expression helps to understand how eddy diffusivities vary across the ocean, and thus how mesoscale eddies impact ocean mixing processes.
Place: Boston MA, USA Publisher: American Meteorological Society
Keywords: Sørishavet; klimamodeller; oseanografi

Geographical distribution of close kin in southern right whales on feeding grounds - Takahashi, Megumi; Førland, Brage; Pastene, Luis A.; Skaug, Hans J. (PLOS ONE, 2024)
This study investigated the close kinship structure of southern right whales on feeding grounds during austral summer seasons. The study was based on biopsy samples of 171 individual whales, which were genotyped with 14 microsatellite DNA loci. Kinship was investigated by using the LOD (Log Odds) score, a relatedness index for a pair of genotypes. Based on a cut-off point of LODPO > 6, which was chosen to balance false positives and negatives, a total of 28 dyads were inferred. Among these, 25 were classified as parent-offspring pairs. Additional genetic (mitochondrial DNA haplotypes) and biological (estimated body length, sex) data were used to provide additional information on the inferred close kin pairs. The elapsed time between sampling varied from 0 (close kin detected in the same austral summer season) to 17 years. All the kin pairs occurred within the Antarctic Indo sector (85°-135°E) and no pair occurred between whales within and outside of this sector. Six pairs were between individuals in high (Antarctic) and lower latitudes. Results of the present analysis on kinship are consistent with the views that whales in the Indo sector of the Antarctic are related with the breeding ground in Southwest Australia, and that whales from this population can occupy different feeding grounds. The present study has the potential to contribute to the conservation of the southern right whales through the monitoring of important population parameters such as population sizes and growth rate, in addition to assist the interpretation of stock structure derived from standard population genetic analyses.
Publisher: Public Library of Science
Keywords: Sørishavet; genetikk; hvaler; marin biologi; zoogeografi

Eccentricity pacing and rapid termination of the early Antarctic ice ages - van Peer, Tim E.; Liebrand, Diederik; Taylor, Victoria E.; Brzelinski, Swaantje; Wolf, Iris; Bornemann, André; Friedrich, Oliver; Bohaty, Steven M.; Xuan, Chuang; Lippert, Peter C.; Wilson, Paul A. (Nature Communications, 2024)
Earth’s obliquity and eccentricity cycles are strongly imprinted on Earth’s climate and widely used to measure geological time. However, the record of these imprints on the oxygen isotope record in deep-sea benthic foraminifera (δ18Ob) shows contradictory signals that violate isotopic principles and cause controversy over climate-ice sheet interactions. Here, we present a δ18Ob record of high fidelity from International Ocean Drilling Program (IODP) Site U1406 in the northwest Atlantic Ocean. We compare our record to other records for the time interval between 28 and 20 million years ago, when Earth was warmer than today, and only Antarctic ice sheets existed. The imprint of eccentricity on δ18Ob is remarkably consistent globally whereas the obliquity signal is inconsistent between sites, indicating that eccentricity was the primary pacemaker of land ice volume. The larger eccentricity-paced early Antarctic ice ages were vulnerable to rapid termination. These findings imply that the self-stabilizing hysteresis effects of large land-based early Antarctic ice sheets were strong enough to maintain ice growth despite consecutive insolation-induced polar warming episodes. However, rapid ice age terminations indicate that resistance to melting was weaker than simulated by numerical models and regularly overpowered, sometimes abruptly.
Article number: 10600
Keywords: Antarktis; geologi; paleoklimatologi; paleoseanografi

Swirls and scoops: Ice base melt revealed by multibeam imagery of an Antarctic ice shelf - Wåhlin, Anna; Alley, Karen E.; Begeman, Carolyn; Hegrenæs, Øyvind; Yuan, Xiaohan; Graham, Alastair G. C.; Hogan, Kelly; Davis, Peter E. D.; Dotto, Tiago S.; Eayrs, Clare; Hall, Robert A.; Holland, David M.; et al. (Science Advances, 2024)
Knowledge gaps about how the ocean melts Antarctica's ice shelves, borne from a lack of observations, lead to large uncertainties in sea level predictions. Using high-resolution maps of the underside of Dotson Ice Shelf, West Antarctica, we reveal the imprint that ice shelf basal melting leaves on the ice. Convection and intermittent warm water intrusions form widespread terraced features through slow melting in quiescent areas, while shear-driven turbulence rapidly melts smooth, eroded topographies in outflow areas, as well as enigmatic teardrop-shaped indentations that result from boundary-layer flow rotation. Full-thickness ice fractures, with bases modified by basal melting and convective processes, are observed throughout the area. This new wealth of processes, all active under a single ice shelf, must be considered to accurately predict future Antarctic ice shelf melt. A unique dataset from beneath an Antarctic ice shelf shows a varied icescape created by differential melt mechanisms.
Publisher: American Association for the Advancement of Science Article number: eadn9188
Keywords: Sørishavet; brehylle; havstrømmer; isbrem; oseanografi

A satellite-derived baseline of photosynthetic life across Antarctica - Walshaw, Charlotte V.; Gray, Andrew; Fretwell, Peter T.; Convey, Peter; Davey, Matthew P.; Johnson, Joanne S.; Colesie, Claudia (Nature Geoscience, 2024)
Terrestrial vegetation communities across Antarctica are characteristically sparse, presenting a challenge for mapping their occurrence using remote sensing at the continent scale. At present there is no continent-wide baseline record of Antarctic vegetation, and large-scale area estimates remain unquantified. With local vegetation distribution shifts now apparent and further predicted in response to environmental change across Antarctica, it is critical to establish a baseline to document these changes. Here we present a 10 m-resolution map of photosynthetic life in terrestrial and cryospheric habitats across the entire Antarctic continent, maritime archipelagos and islands south of 60° S. Using Sentinel-2 imagery (2017–2023) and spectral indices, we detected terrestrial green vegetation (vascular plants, bryophytes, green algae) and lichens across ice-free areas, and cryospheric green snow algae across coastal snowpacks. The detected vegetation occupies a total area of 44.2 km2, with over half contained in the South Shetland Islands, altogether contributing just 0.12% of the total ice-free area included in the analysis. Due to methodological constraints, dark-coloured lichens and cyanobacterial mats were excluded from the study. This vegetation map improves the geospatial data available for vegetation across Antarctica, and provides a tool for future conservation planning and large-scale biogeographic assessments.
Keywords: Antarktis; alger; biodiversitet; botanikk; lav; planter

Highly stratified mid-Pliocene Southern Ocean in PlioMIP2 - Weiffenbach, J. E.; Dijkstra, H. A.; von der Heydt, A. S.; Abe-Ouchi, A.; Chan, W.-L.; Chandan, D.; Feng, R.; Haywood, A. M.; Hunter, S. J.; Li, X.; Otto-Bliesner, B. L.; Peltier, W. R.; et al. (Clim. Past, 2024)
During the mid-Pliocene warm period (mPWP; 3.264–3.025 Ma), atmospheric CO2 concentrations were approximately 400 ppm, and the Antarctic Ice Sheet was substantially reduced compared to today. Antarctica is surrounded by the Southern Ocean, which plays a crucial role in the global oceanic circulation and climate regulation. Using results from the Pliocene Model Intercomparison Project (PlioMIP2), we investigate Southern Ocean conditions during the mPWP with respect to the pre-industrial period. We find that the mean sea surface temperature (SST) warming in the Southern Ocean is 2.8 °C, while global mean SST warming is 2.4 °C. The enhanced warming is strongly tied to a dramatic decrease in sea ice cover over the mPWP Southern Ocean. We also see a freshening of the ocean (sub)surface, driven by an increase in precipitation over the Southern Ocean and Antarctica. The warmer and fresher surface leads to a highly stratified Southern Ocean that can be related to weakening of the deep abyssal overturning circulation. Sensitivity simulations show that the decrease in sea ice cover and enhanced warming is largely a consequence of the reduction in the Antarctic Ice Sheet. In addition, the mPWP geographic boundary conditions are responsible for approximately half of the increase in mPWP SST warming, sea ice loss, precipitation, and stratification increase over the Southern Ocean. From these results, we conclude that a strongly reduced Antarctic Ice Sheet during the mPWP has a substantial influence on the state of the Southern Ocean and exacerbates the changes that are induced by a higher CO2 concentration alone. This is relevant for the long-term future of the Southern Ocean, as we expect melting of the western Antarctic Ice Sheet in the future, an effect that is not currently taken into account in future projections by Coupled Model Intercomparison Project (CMIP) ensembles.
Publisher: Copernicus Publications
Keywords: Sørishavet; geologi; klimamodeller; klimatologi; oseanografi; paleoklimatologi

Gross Primary Production of Antarctic Landfast Sea Ice: A Model-Based Estimate - Wongpan, Pat; Meiners, K. M.; Vancoppenolle, M.; Fraser, A. D.; Moreau, Sebastien; Saenz, B. T.; Swadling, K. M.; Lannuzel, D. (Journal of Geophysical Research: Oceans, 2024)
Much of the Antarctic coast is covered by seasonal landfast sea ice (fast ice), which serves as an important habitat for ice algae. Fast-ice algae provide a key early season food source for pelagic and benthic food webs, and contribute to biogeochemical cycling in Antarctic coastal ecosystems. Summertime fast ice is undergoing a decline, leading to more seasonal fast ice with unknown impacts on interconnected Earth system processes. Our understanding of the spatiotemporal variability of Antarctic fast ice, and its impact on polar ecosystems is currently limited. Evaluating the overall productivity of fast-ice algae has historically been hampered by limitations in observations and models. By linking new fast-ice extent maps with a one-dimensional sea-ice biogeochemical model, we provide the first estimate of the spatio-seasonal variability of Antarctic fast-ice algal gross primary production (GPP) and its annual primary production on a circum-Antarctic scale. Experiments conducted for the 2005?2006 season provide a mean fast ice-algal production estimate of 2.8 Tg C/y. This estimate represents about 12% of overall Southern Ocean sea-ice algae production (estimated in a previous study), with the mean fast-ice algal production per area being 3.3 times higher than that of pack ice. Our Antarctic fast-ice GPP estimates are probably underestimated in the Ross Sea and Weddell Sea sectors because the sub-ice platelet layer habitats and their high biomass are not considered.
Publisher: John Wiley & Sons, Ltd Article Number: e2024JC021348
Keywords: Sørishavet; alger; biogeokjemi; geofysikk; havis; oseanografi; sjøis

Re-evaluating winter carbon sink in Southern Ocean by recovering MODIS-Aqua chlorophyll-a product at high solar zenith angles - Zhang, Ke; Zhang, Zhaoru; He, Jianfeng; Smith, Walker O.; Liu, Na; Le, Chengfeng (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)
Satellite ocean color observations are extensively utilized in global carbon sink evaluation. However, the valid coverage of chlorophyll-a concentration (Chla, mg m−3) measurements from these observations is severely limited during autumn and winter in high latitude oceans. The high solar zenith angle (SZA) stands as one of the primary contributors to the reduced quality of Chla products in the high-latitude Southern Ocean during these seasons. This study addresses this challenge by employing a random forest-based regression ensemble (RFRE) method to enhance the quality of Moderate Resolution Imaging Spectroradiometer (MODIS) Chla products affected by high SZA conditions. The RFRE model incorporates the color index (CI), band-ratio index (R), SZA, sensor zenith angle (senz), and Rayleigh-corrected reflectance at 869 nm (Rrc(869)) as predictors. The results indicate that the RFRE model significantly increased the MODIS observed Chla coverage (1.03 to 3.24 times) in high-latitude Southern Ocean regions to the quality of standard Chla products. By applying the recovered Chla to re-evaluate the carbon sink in South Ocean, results showed that the Southern Ocean’s ability to absorb carbon dioxide (CO2) in winter has been underestimated (5.9–18.6 Tg C year−1) in previous assessments. This study underscores the significance of improving the Chla products for a more accurate estimation of winter carbon sink in the Southern Ocean.
Keywords: Sørishavet; fjernmåling; fotogrammetri; karbon syklus; karbondioksid; oseanografi